Tactile sensor formed on polyimide film with high total light transmittance and switch device using the same
By printing a tactile sensor on a polyimide film, the problem of forming a stable and low-cost tactile sensor on a polymer film in the prior art is solved, and a lightweight, thin, soft and tough sensor is formed on the curved surface, and the yield and transparency are improved, meeting the market's demand for low-cost and high-performance electronic devices.
Patent Information
- Application Number
- CN202080044446.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-19
- Filing Date
- 2020-06-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-06-15
AI Technical Summary
The prior art is difficult to form stable and low-cost tactile sensors on polymer films, especially on curved surfaces or complex shapes, and the yield and transparency of the sensors are not sufficient to meet market demand.
A tactile sensor is formed on a polyimide film by printing technology. The glass transition temperature of the film is set to be 250°C or higher and 310°C or lower, the tensile strength is 250 MPa or lower, the elongation is 30% or lower, the total light transmittance is 80% or higher, and the polar component of the surface free energy is 1.5mJ/m2 to 10mJ/m2. The switch function is realized by contacting the electrodes such as fingers and making a voltage signal, and the noise is controlled through electronic circuits.
It realizes the formation of lightweight, thin, soft and strong tactile sensors on the curved surfaces of planes and three-dimensional objects, with high yield and high all-light transmittance, which can effectively detect weak pressure and drive other devices, meeting the market's demand for low-cost and high-performance electronic devices.
Smart Images

Figure CN114008424B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a touch sensor formed on a polyimide film having high total light transmittance and a switch device using the same. Background Art
[0002] In recent years, in the field of electronic devices, printed electronics technology (printed electronics) that uses printing technology to make electronic devices has attracted attention. There are new technical elements in printed electronics technology that can be roughly classified into two categories. First, through the wiring formation technology using metal particle ink or metal paste, which has been actively promoted and developed in recent years, the process has been simplified and the cost has been reduced, which has not been achieved by the lithography method used in the past. Second, the rigid printed circuit board (PCB) is replaced with a polymer film with special features such as thinness or softness and stretchability, so that the electronic device can be made thinner or more flexible. Metal particle ink or metal paste is bonded to the polymer film at the interface, which has a great impact on the wiring formability.
[0003] That is, there is the following feature: as expressed by the well-known Young's equation, the formation state of the wiring is determined by the relationship between the surface free energy of the liquid or paste-like metal particle ink or metal paste and the solid polymer film. Microscopically, the surface free energy is affected by the chemical composition of the metal particle ink or metal paste and the polymer film, that is, the dispersion and polarity at the molecular level. Therefore, understanding the surface free energy is particularly important in printed electronics technology.
[0004] In the above technical background, the target market is the field of trillion (one trillion) sensors (including printed electronics, laser, image, etc.), organic electroluminescence (EL), and organic transistors, and the fifth generation society (super intelligent society) or 5.0 society is aimed at 2020 to 2030. It is necessary to carry out technological innovation to reduce or solve the problems of population decline and aging, energy, environment and disasters, and widening regional disparity issues that are future problems through the fourth industrial revolution (IoT, big data, AI (artificial intelligence) robots, etc.).
[0005] The goal of the fourth industrial revolution is to create a society where all objects are connected to the Internet (hereinafter referred to as IoT (short for Internet of Things)), information obtained from the objects is accumulated into big data, and valuable feedback is provided to us through analysis using AI. In the past, personal computers, smartphones, tablets, TVs, etc. were connected to the Internet, but in the future, the scope of connection is expected to expand to mobile tools (cars, trains, airplanes, ships, transport trucks, etc.), homes (refrigerators, TVs, air conditioners, vacuum cleaners and other home appliances or security systems, etc.), and medical care facilities (beds, health status monitoring, etc.). For example, the goal is to predict future congestion based on the location information of the car and provide the driver with this information or realize autonomous driving; to provide a comfortable temperature and humidity environment or dimming based on the temperature, humidity, and brightness information in the house; to reduce the burden of status monitoring that previously relied on manual labor by monitoring the health status of patients in medical care facilities, etc.
[0006] However, it is not enough to simply realize such a network. According to the "Survey on the Composition Ratio of Raw Materials for Automobile Production" by the Japan Automobile Manufacturers Association, ordinary small cars in the 1980s had sharp edges and a heavy shape because they used as much as 73% to 75% steel, only 3% aluminum, and 6% to 7% resin materials. After 2000, the proportion of steel decreased to about 70%, aluminum increased to 6%, and resin materials increased to 8%, thus changing to a round or curvaceous shape that took advantage of the special features of aluminum and resin materials to keep pace with the improvement in fuel consumption brought about by the lightweight body. For home appliances such as refrigerators, televisions, air conditioners, and robot vacuum cleaners, various sizes or suitability of interior decoration in homes, or design according to personal preferences are also emphasized, and curved shapes that give a soft impression are gradually becoming widely accepted. For medical care facilities, in order to collect accurate life information, it is necessary to provide health care equipment that can be worn by patients and fit the body, so shapes that are not soft or have no curves are inappropriate. In other words, it is necessary to recognize that objects used in the future IoT society have various curves.
[0007] In addition, in the field of robots that were previously only used in factory production lines, communication robots that provide services in places close to humans have appeared in recent years. It is recognized that such robots will play a big role in the future IoT society by connecting them to the Internet. In order for robots and humans to establish a smooth relationship, it is necessary for humans to make robots "easy to approach". In terms of the above point of view, it is believed that the shape of the robot that is perceived visually or tactilely will have a great influence, so it is not an exaggeration to say that a smooth curved surface shape or a balance of moderate hardness and softness will determine whether robots will be popularized in general life.
[0008] Such future cars, home appliances, health care equipment, robots, etc. will change to have further curved shapes, and in order to realize the IoT society, it is necessary to install sensors on objects to extract information such as position, temperature, humidity, illumination, pressure, etc. In this context, in recent years, in addition to the development of sensors with three-dimensional structures with curved surfaces and concave-convex surfaces, and sensor modules using raw materials that are soft and suitable for curved surfaces, the development of the above-mentioned technologies in the field of printed electronic technology, such as printing devices, printing materials, and substrate materials for forming circuit wiring on curved surfaces and concave-convex surfaces, has become more important.
[0009] In order to realize the IoT society, it is necessary to provide a large number of various electronic devices to society at a low price. It is believed that sensors manufactured using printed electronics technology must reach the price required by users in the future, that is, less than 500 yen per sensor module.
[0010] In addition, as mentioned above, printed electronics technology is a wiring formation technology using metal particle ink or metal paste, which is different from lithography, but by combining it with integrated circuits (ICs) manufactured using printing technology and existing lithography technology as "flexible hybrid electronics technology", it is possible to economically realize flexible products or parts while maintaining high performance. This concept is a technology promoted mainly in the United States. As a whole, the product can provide excellent physical properties such as light weight, thin film, softness and toughness in addition to low cost and high performance, and is expected to be used in unprecedented applications.
[0011] As the polymer film substrate, plastics such as polyethylene terephthalate (hereinafter referred to as PET), polyethylene naphthalate (hereinafter referred to as PEN), polyetheretherketone (hereinafter referred to as PEEK), polyphenylene sulfide (hereinafter referred to as PPS), polyarylate (hereinafter referred to as PAR), polyimide (hereinafter referred to as PI), polycarbonate (hereinafter referred to as PC), triacetyl cellulose (hereinafter referred to as TAC), cellulose acetate propionate (hereinafter referred to as CAP) can be used (Patent Document 1). By using such a polymer film, it is possible to achieve a lighter and thinner film than when using a glass substrate or the like.
[0012] Furthermore, in order to cope with the above-mentioned future problems of population decline and aging, health care devices that are attached to the human body, clothes, or inserted into bedding to monitor health status have attracted attention in recent years. For example, Patent Document 2 discloses a device that uses a vibration sensor to detect the respiratory activity of the lungs and the pulsation of the heart on a sleeping bed laid on the bed and the floor, and can detect the health status of a person 24 hours a day. The problem to be solved is to reduce the burden of nursing work by monitoring the status of patients and the elderly who are sleeping in bed. In Patent Document 2, polyvinylidene fluoride is used in a vibration sensor to detect the respiratory activity of the lungs and the pulsation of the heart.
[0013] The polyvinylidene fluoride is a piezoelectric material that converts mechanical energy into electrical energy or converts electrical energy into mechanical energy. As shown in the above-mentioned patent document 2, the following technical development is being actively carried out in recent years: using piezoelectric materials, detecting the biological signals represented by the respiratory activity of the lungs and the beating of the heart, that is, capturing the biological signals as mechanical energy, converting them into electrical energy through piezoelectric materials, and monitoring the technology, but also making a detection device with a multi-touch function that can track the input pressure. It is to convert the pressure (referring to mechanical energy) applied to the polyvinylidene fluoride into voltage (referring to electrical energy), amplify, remove noise, add, analog-to-digital conversion, and monitor the pressure on a computer, thereby being used for touch panels, energy harvesters, environments with care (also known as smart boards (Intelligent floor)) or guard applications (patent document 3).
[0014] In addition, as a device for detecting the input pressure, there is a classic push button switch mounted on a base substrate on which electrodes are formed. The push button switch comprises: a base configured as a box into which an operation button can be pressed, a connection terminal protruding from the bottom surface of the base facing the base substrate and capable of connecting to the electrode, and a connection terminal extending toward the bottom surface, and the base is pressed toward the base substrate, thereby detecting the input pressure (Patent Document 4).
[0015] Furthermore, a pressure sensor including a piezoelectric material is disclosed in Patent Document 5. This is a structure in which a piezoelectric material is combined with a field effect transistor structure, and it is considered to be an analog proximity switch in that it has a function of passing a current proportional to an applied stress.
[0016] In addition, pressure sensors include not only sensors using piezoelectric materials, but also devices that detect the amount of deformation caused by pressure as a change in resistance. This device has the following structure: a concave portion is formed by etching the bottom surface of a single crystal silicon substrate, a pressure strain portion exposed on the bottom surface of the concave portion is made, and the pressure strain portion includes a strain gauge provided on the active layer above the concave portion and a conductive layer formed by sandwiching an insulating layer on the active layer (Patent Document 6).
[0017] Patent Document 7, regarding pressure sensors, gripping devices, and robots, mentions that: even though PVDF is flexible, its deformation range is within the strain range of the material, and its Young's modulus is about 2 GPa, which is hard as a sensor material requiring high sensitivity, and points out that: as a pressure sensor that utilizes the so-called piezoelectric phenomenon that generates a voltage signal through material deformation, when PVDF is used, there are the following problems. That is, it takes time to apply a sufficient load to deform PVDF, and the time from the moment the pressure sensor contacts the object to be gripped to the start of outputting the voltage signal becomes longer, and the pressure detection sensitivity at the time of contact is reduced, which becomes significant especially when the object to be gripped is a soft object, so sponges of rubber compositions such as silicone are suitable.
[0018] Similarly, in Patent Document 8, there is a similar invention relating to a pressure sensing sensor mounting wiring board that can be well used as a pressure sensing sensor represented by a skin tactile sensor of a humanoid robot, and the piezoelectric plastic film is preferably a porous piezoelectric plastic film. The reason is believed to be that the porous piezoelectric plastic film has piezoelectricity and does not have pyroelectricity, and therefore has the advantage of being less susceptible to temperature changes. In addition, a voltage is generated only due to stress in the thickness direction, and a voltage caused by stretching in the surface direction is almost not generated. Therefore, there is no need to consider the elongation in the surface direction to determine the arrangement interval of the pressure sensing sensor, and it is easy to increase the number of pressure sensing parts. In addition, the PVDF piezoelectric plastic film is easy to sense noise, and in order to reduce the occurrence of such noise, it is necessary to increase the arrangement interval of the pressure sensing sensor to a certain extent, and there is a limit to the increase in the number of pressure sensing parts. In a porous plastic film pressure sensing sensor, a voltage is generated only due to stress in the thickness direction, and a voltage caused by stretching in the surface direction is almost not generated. Therefore, there is no need to consider the elongation in the surface direction to determine the arrangement interval of the pressure sensing sensor, and it is easy to increase the number of pressure sensing parts.
[0019] So far, the invention of sensors for health care devices, switches, and robot applications has been exemplified, and in such applications, the sensors are beginning to be required to be applicable to three-dimensional objects with curved surfaces. That is, in order to realize the IoT society, it is necessary to install sensors on objects to extract information such as position, temperature, humidity, illumination, and pressure. However, from the perspective of design, in recent years, the objects are mostly three-dimensional objects with curved surfaces or concave-convex surfaces, and sensors using raw materials that are soft and suitable for such surfaces are beginning to be developed. In addition, it is expected that the printed electronics technology such as printing devices, printed materials, and substrate materials used to form circuit wiring on curved surfaces or concave-convex surfaces can contribute as an element technology.
[0020] As an example of active research and development in forming sensors or circuit wiring on curved surfaces, Patent Document 9 discloses the following: By using a conductive paste that does not cause disconnection of the conductive part even when heated and stretched, and has excellent adhesion, a three-dimensional printed circuit or touch sensor can be made. Specifically, a conductive paste for forming processing using condensed silver particles is printed on a thermoplastic resin substrate with a glass transition temperature of 80°C or less by screen printing, and then vacuum-formed into a three-dimensional structure by heating and deforming. The feature is that during this forming, the conductive part follows the forming shape and stretches and deforms to 140%, and no disconnection occurs at this time. However, it is impossible to directly form the conductive part on a curved three-dimensional structure.
[0021] In addition, Patent Document 10 discloses the following method: a flat electrostatic capacitive touch panel substrate with electrodes formed by sputtering is thermally formed into a three-dimensional shape by using heat deformation to produce an electrostatic capacitive curved touch panel substrate. In this method, the thermoforming temperature is set to 190°C, and transparent resins such as acrylic resin (PMMA), polycarbonate (PC), cycloolefin polymer (COP), polyethylene terephthalate (PET) having heat resistance characteristics higher than this temperature are used as panel substrates. Patent Documents 9 and 10 are both electrostatic capacitive sensors produced by heating and deforming them.
[0022] On the other hand, as described above, a large number of piezoelectric sensors that use piezoelectric materials that convert mechanical energy into electrical energy or electrical energy into mechanical energy instead of electrostatic capacitance have been developed, but they are generally made using a planar laminate as exemplified in Patent Documents 2 and 3. In addition, these piezoelectric sensors generally use the property of converting mechanical energy into electrical energy, the mechanical energy being deformation due to pressure, and the electrical energy being a voltage signal.
[0023] In addition, an offset printing device has been developed as a printing device for forming circuit wiring on a curved surface. According to this method, there are a printing plate, a rubber blanket, and a carrier for fixing and transporting a printed object, a first mechanism in which the surface of the printing plate contacts the surface of the rubber blanket and moves relative to each other, and a second mechanism in which the surface of the rubber blanket contacts the surface of the printed object fixed on the carrier and moves relative to each other. The rubber blanket uses a material in which PDMS rubber is wound on a metal cylinder. The conductive metal paste received by the PDMS rubber is deformed in a manner that conforms to the shape of a curved surface or a concave-convex surface, and is printed. The printed circuit wiring has conductivity through subsequent heating and calcination (Patent Document 11).
[0024] Prior art literature
[0025] Patent Literature
[0026] Patent Document 1: Japanese Patent No. 6259390
[0027] Patent Document 2: Japanese Patent No. 6369919
[0028] Patent Document 3: Japanese Patent Application Laid-Open No. 2018-136954
[0029] Patent Document 4: Japanese Patent No. 6447492
[0030] Patent Document 5: Japanese Patent No. 6008970
[0031] Patent Document 6: Japanese Patent No. 4965274
[0032] Patent Document 7: Japanese Patent No. 6471812
[0033] Patent Document 8: Japanese Patent Application Laid-Open No. 2013-178241
[0034] Patent Document 9: WO2019 / 039209
[0035] Patent Document 10: WO2015 / 045325
[0036] Patent Document 11: Japanese Patent No. 6517058 Summary of the invention
[0037] Problems to be solved by the invention
[0038] However, not all polymer films shown in Patent Document 1 are applicable to all printed electronic technologies. Functional electronic materials such as metal paste or metal particle ink used for forming electrodes and wiring, and the piezoelectric material require a heating temperature of 100°C to 200°C. Heating at a temperature above the glass transition temperature of the polymer film does not necessarily mean that the polymer film is deformed to a state that cannot be used as a substrate, but since it changes to a rubbery state under the condition of applying stress to the polymer film, the printed circuit is offset from the designed position, causing deformation such as skewness of the polymer film substrate. The glass transition temperature of PET is 77°C, and the glass transition temperature of PPS is 100°C. When calcined at 100°C to 200°C under the condition of applying stress, they both cause deformation, so they are not suitable. In addition, since the glass transition temperature of PEN, PEEK, PPS, PAR, and PC exceeds 100°C, they can withstand calcination at 100°C to 200°C under the condition of applying stress, but on the other hand, these polymers are difficult to form a film substrate by a solution process and are not suitable for the purpose of thin filming.
[0039] Furthermore, colored PI such as Upilex (registered trademark) or Kapton (registered trademark) has a yellow to brown color, and the transparency of electronic devices using it as a polymer film substrate is low. In the latest development of electronic devices, transparency is emphasized for such devices. If the consumer's requirements such as "integrating into daily life" and "inadvertently existing" are considered, there is a problem of being conspicuous in the place of use. Furthermore, the most important thing is that if the polymer film is used as a substrate, the electrode will be poorly formed when the conductive ink or paste is printed and calcined, and there is a problem that the defective rate of electronic device products below 0.1% that cannot meet the market requirements is expected. From the perspective of protecting the economy of consumers, ensuring quality, and preventing accidents, it is expected that the yield rate will preferably be at least 98.0%, and more preferably 99.9% or more.
[0040] The detection devices shown in the above-mentioned Patent Documents 2 and 3 can be monitored in real time by a computer, but the pressure applied to the device cannot be detected instantly and easily by human vision, touch, hearing, etc. In addition, the detection device with PET as a substrate is made by forming electrodes and a ferroelectric layer showing piezoelectricity by printing, and calcining at 100°C for a short time. However, depending on the type of solvent or additive contained in the electrode and the ferroelectric layer required for printing, there is a concern that malfunction may occur due to insufficient removal during calcination at 100°C for a short time. Furthermore, as mentioned above, calcination at a high temperature of more than 100°C for a long time is likely to cause deformation of PET, so it is not appropriate.
[0041] The push button switch shown in Patent Document 4 is widely used and cheap, but the button protrudes from the base substrate by at least millimeters and cannot be thinned to micrometers. In addition, the switch needs to be set on a flat surface, which is difficult to conform to complex shapes such as curved surfaces.
[0042] Furthermore, it is believed that the pressure sensor shown in the above-mentioned patent document 5 will not respond to weak pressure. In addition, since the gate electrode, source electrode, and drain electrode constituting the field effect transistor are arranged in the substrate, there is a problem that a complex shape needs to be formed. Furthermore, PEN and PI are used in the lower substrate, but there are the following problems: on Teonex (registered trademark) as a polymer film of PEN, Upilex (registered trademark) as a yellow to brown polymer film of PI, Kapton (registered trademark), a uniform electrode surface and a piezoelectric material surface are formed by a printing method, and the switching device formed by the piezoelectric material has a low yield rate of stable driving.
[0043] In addition, considering the thin film formation by the solution process, PEN is difficult to be solubilized by an organic solvent. Furthermore, considering the inconspicuousness in the parts where electronic devices are used, yellow to brown PI such as Upilex (registered trademark) and Kapton (registered trademark) are visually conspicuous due to their low total light transmittance in the visible wavelength range, and are therefore not ideal.
[0044] In addition, the pressure sensor shown in the above-mentioned Patent Document 6 uses single crystal silicon, so its thickness is limited and it does not have the lightness and softness of a polymer film. Moreover, for this resistance variable type device, the electronic device does not work unless pressure is applied continuously, so it is not suitable as an electronic device that switches between the on state and the off state by applying pressure once.
[0045] Furthermore, although the pressure-sensitive sensors or pressure-sensing sensors for robots exemplified in Patent Documents 7 and 8 have excellent detection capabilities, they are not sensors that take into account the strain stress when the sensors are formed three-dimensionally. Instead, they are sensors that seek to function as surface sensors for the fingers of the robot. Furthermore, if the piezoelectric sensing function of a porous or sponge state is sought, repeated contact impacts will not feel realistic.
[0046] Patent Documents 9 and 10, which are inventions of forming sensors on curved surfaces, are electrostatic capacitance sensors that detect changes in weak current or charge, and can sense contact with biological bodies, but since contact with non-biological objects does not cause changes in current, it cannot be sensed. Moreover, since the electrostatic capacitance sensors on these curved surfaces are accompanied by the elongation of the conductive part during forming, the wiring resistance increases, and when multiple functional layers are stacked, the curvature of each layer is different, so the raw materials that can be used are limited, and it is impossible to simply assemble the sensor in a small amount of multiple varieties and a three-dimensional structure with various curved surfaces. On the other hand, piezoelectric sensors have nothing to do with biological bodies or non-biological bodies, and generate voltage through deformation caused by pressure, so they can sense tiny contacts with various objects. Therefore, if piezoelectric sensors can be formed on three-dimensional objects with curved surfaces and concave and convex surfaces, it can be expected to expand the changes in the sensed object. In addition, although simple circuit wiring can be formed on a three-dimensional structure by printing methods (Patent Document 11), it is necessary to develop a technology for detecting the sensor function of information received from the outside world.
[0047] As mentioned above, printed electronics technology is positioned as a very important technology in the industry, and active research and development is being promoted. The inexpensive, lightweight, thin-film polymer film substrate formed by drawing wiring, piezoelectric materials and other functional electronic materials using coating printing technology and calcining them, and the electronic devices made from the substrate can be used for welfare medical purposes, wearable device purposes, RFID purposes, transistors for smartphones, tablet terminals, computers, displays, etc., sensors or control parts for medical, nursing beds, anti-theft, childcare, self-driving cars, pet robots, drones, etc., and electronic parts for organic EL, liquid crystal displays, lighting, automobiles, robots, electronic glasses, music players, etc. In addition, as a solution to the problem of solving future problems, it is necessary to provide electronic devices with sensor functions that are flexible, soft, and followable to various three-dimensional shapes.
[0048] According to the present invention, a tactile sensor with stable driving and a device with a switch function using the tactile sensor can be provided with a high yield rate. The tactile sensor is lightweight, soft and strong, so it can be applied to various three-dimensional objects such as flat surfaces and curved surfaces of three-dimensional objects. The total light transmittance of the film used as the substrate is high, so it is inconspicuous at the location where it is arranged. The tactile sensor can be made into a thin film by forming a polymer film from a varnish.
[0049] Means of solving problems
[0050] The present invention relates to a switch device, which is a tactile sensor, comprising: a first electrode printed on the surface of a polyimide film, a ferroelectric layer printed in a manner covering the first electrode, and a second electrode printed in a manner overlapping the first electrode with the ferroelectric layer sandwiched therebetween, wherein the polyimide film has a glass transition temperature of 250° C. to 310° C., a tensile strength of 250 MPa or less, an elongation of 30% or less, a total light transmittance of 80% or more, and a polar component of surface free energy of 1.5 mJ / m 2 ~10mJ / m 2 , and has a specific high total light transmittance; in the switching device, the tactile sensor generates a voltage signal through contact with the electrode by a biological body such as a finger, and the electronic circuit controls the noise from the biological body and the environment mixed in the voltage signal, thereby prompting the driving of other devices.
[0051] Effects of the Invention
[0052] According to the present invention, a switching device can be provided with a high product yield. The switching device can be formed on surfaces of various shapes, such as planes and curved surfaces of three-dimensional objects, and is lightweight, thin, flexible and strong. The device can drive other devices by slight contact with a sensor portion. The sensor portion is composed of electrodes, ferroelectrics and a polyimide film having a specific high total light transmittance using a printing technique that matches the color tone of the configured periphery. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It means using Gaussian curvature 0cm -2 When the support body is formed into a tactile sensor, and the absolute value of 0.04 cm is used -2 The following is a diagram of a stacked structure when a support body with Gaussian curvature is used to form a tactile sensor.
[0054] Figure 2 The waveform of the generated voltage is shown when a finger touches the touch sensor part, which is transformed by the human body itself and the noise received by the human body from the environment.
[0055] Figure 3 This is a diagram showing a circuit example when an RC low-pass filter is used to remove noise of a commercial power supply frequency (50 Hz) and the frequency dependence of its gain.
[0056] Figure 4 This is a diagram showing a circuit example of a Sallen-Key low-pass filter for removing commercial power frequency (50 Hz) noise and the frequency dependence of its gain.
[0057] Figure 5 It means by Figure 4 The circuit suppresses Figure 2 A graph of the voltage signal after the noise is shown.
[0058] Figure 6 The diagram shows an electronic circuit, that is, a switch device, connected to the tactile sensors of Examples 1 to 6 and having a switching function for controlling voltage changes caused by noises received by the human body itself and by the environment.
[0059] Figure 7 The present invention represents a voltage signal on which the noise generated by the tactile sensor of the switching device manufactured in Example 1 is superimposed, for example, when the tactile sensor is touched by a finger, and a situation in which the on-state voltage and the off-state voltage are switched by controlling the noise, thereby causing the LED to light up and turn off, and the oscillator to be driven and stopped.
[0060] Figure 8 This is a diagram showing that, for example, the electronic circuit used for comparison in Comparative Example 6 cannot control the noise to which the human body itself or the noise to which the human body is exposed from the environment.
[0061] Fig. 9 Indicates the use Figure 8 When the electronic circuit is in a state of being touched, even if the touch sensor is touched with a finger, the voltage change between the on state and the off state cannot be switched. DETAILED DESCRIPTION
[0062] Hereinafter, embodiments of the present invention will be described.
[0063] Since then, use Figure 1 The structure of the touch sensor of this embodiment is described below. The polyimide film 2 of this embodiment is supplied in the form of a film and fixed at a Gaussian curvature of 0 cm. -2 On the surface of a support (hereinafter referred to as a planar support) 1, a polyimide film 2 is formed by coating a varnish described later on the surface of the planar support 1, or by forming a polyimide film 2 on a surface having an absolute value of 0.04 cm -2 The polyimide film 2 is formed by applying a varnish described later on the surface of the support body (hereinafter referred to as a three-dimensional support body) 1' having a Gaussian curvature, and is used in a state of being attached to these surfaces. In addition, the plane support body 1 or the three-dimensional support body 1' is only a support body required in the manufacturing process of the tactile sensor. After the tactile sensor is manufactured, it can be used in a state of being attached to the surface of the plane support body 1 or the three-dimensional support body 1', or it can be peeled off and attached to another plane or three-dimensional object for use.
[0064] When a polyimide film 2 in a film state is supplied and fixed on a plane support 1 to prepare a support for printing the first electrode 3, the ferroelectric layer 4, and the second electrode 5 described later, the printing is usually performed at a temperature of 10°C to 40°C, so the plane support 1 can be used even if it has low heat resistance. Specifically, it is glass, metal, plastic, etc. There is no particular limitation on glass, and there are soda-lime glass, quartz glass, borosilicate glass, etc. In addition, there is no particular limitation on metal, and alloys such as iron, aluminum, titanium, nickel, copper, silver, tungsten, platinum, gold, and stainless steel can be used. As for plastics, even raw materials such as polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), and PET, which may not be considered to have high heat resistance, can be used without problems. However, this is limited to the printing process. In the heating process of the first electrode 3, the ferroelectric layer 4, and the second electrode 5 described later, when heating is performed in a state fixed on the plane support 1, it is necessary to consider the heating temperature conditions to select the plane support 1.
[0065] On the other hand, when the polyimide film 2 is formed by applying the varnish described later on the surface of the planar support 1 or on the surface of the three-dimensional support 1', for the support, glass or metal can use the same raw materials as above, but plastics must be particularly limited. Specifically, the varnish is a polyamic acid varnish as the starting material of the polyimide film 2, which needs to be dehydrated and cyclized by heating at 280°C to 320°C, so the support requires heat resistance of 280°C to 320°C. Therefore, it is preferably selected from plastics such as polyphenylene sulfide (PPS), polyimide (PI), polytetrafluoroethylene (PTFE), polyamide-imide (PAI) that show heat resistance at this temperature.
[0066] The three-dimensional support body 1' of the present embodiment is described. With respect to a surface represented by Gaussian curvature, a plane containing the normal vector can be taken from a normal vector perpendicular to the surface for any point on the surface. According to the overlap of the plane and the surface, a cross-sectional line represented by two-dimensional coordinates can be obtained. When the cross-sectional line is a curve, the curvature (the inverse of the radius of the arc when the curve is approximated as an arc) is obtained by approximating the curve to an arc. According to the overlap of the plane in each direction of 360° containing the normal vector and the curved surface, when the cross-sectional line is taken in each direction of 360°, the curvature in each direction of 360° is obtained. The product of its maximum and minimum values is called Gaussian curvature, and the state of the curved surface can be quantified. In addition, when the Gaussian curvature is a positive value, it represents a convex curved surface, and when the Gaussian curvature is a negative value, it represents a concave curved surface. In addition, although the sharpness or smoothness of the surface cannot be understood sensorily from the absolute value of the Gaussian curvature, if each curve is observed, the larger the curvature, the sharper the curve is, and the smaller the curvature, the smoother the curve is.
[0067] When the surface is a plane, since the cross-section line is a straight line, if the straight line is approximated by a circle, it is approximated to a circle with an infinite radius, so the minimum value of the curvature is 0. Therefore, the Gaussian curvature is 0. The side of a cylinder or a cone feels like a curved surface, but when the normal vector of any point on the curved surface is taken, and the plane containing the normal vector is taken, and the overlap between the plane and the curved surface is observed, the cross section appears as a quadrilateral in the case of a cylinder and as an isosceles triangle in the case of a cone, so the cross-section line is a straight line, so the minimum value of the curvature is 0, and therefore the Gaussian curvature is 0.
[0068] It can be seen that the absolute value of the Gaussian curvature in this embodiment is 0.04 cm -2 In the case of a curved surface that can be approximated as a sphere, it is preferable to have a curved surface with a radius of curvature defined as the inverse of the curvature of 5 cm or more. Since the absolute value of the Gaussian curvature is set to 0.04 cm -2Therefore, a plane having a Gaussian curvature of 0, a cylinder, and a side surface of a cone are also included in the present embodiment.
[0069] When the absolute value of Gaussian curvature is greater than 0.04 cm -2 In the case of a curved surface, the formation of the polyimide film 2, the first electrode 3, the ferroelectric layer 4, and the second electrode 5 to be formed on the three-dimensional support 1' described later will be difficult. The polyimide film 2, the first electrode 3, the ferroelectric layer 4, and the second electrode 5 in this embodiment are formed on the three-dimensional support 1' by printing or coating in a liquid state such as varnish, paste, ink, etc., so the absolute value of the Gaussian curvature is greater than 0.04 cm -2 The more components with low surface tension are contained, the more significant this phenomenon is. This is important when forming any layer, and is particularly significant in the following varnishes: the varnish has a high effect of reducing surface tension described later, and is used in the formation of the ferroelectric layer 4 using a copolymer composed of vinylidene fluoride and trifluoroethylene containing fluorine atoms as constituent units.
[0070] The present invention clarifies that when the thickness is formed on the curved surface, due to the influence of the surface tension, the absolute value of the Gaussian curvature has an upper limit, that is, the sharpness of the curved surface has an upper limit. The absolute value of the Gaussian curvature is greater than 0.04 cm -2 In the case of a curved surface, it was confirmed that the varnish of the ferroelectric layer in particular flowed, and as a result, it was confirmed that a uniform layer without defects could not be formed.
[0071] In addition, the varnish for forming the polyimide film 2, the paste for making the first electrode 3 and the second electrode 5, and the ink which do not have a low surface tension like the varnish for the ferroelectric layer 4, can also sometimes have an absolute value of Gaussian curvature greater than 0.04 cm. -2 However, if the absolute value of the Gaussian curvature is greater than 1 cm -2 , not only will the problem of the flow of the paste or ink arise, but also the problem that the printing device cannot cope with. For this reason, in this embodiment, the absolute value of the Gaussian curvature is appropriately 0.04 cm -2 the following.
[0072] The polyimide film 2 with high total light transmittance of the present embodiment is characterized in that it is a polyimide film formed by reacting a diamine compound with an alicyclic structure with tetracarboxylic dianhydride, has a glass transition temperature of 250°C or higher and 310°C or lower, a tensile strength of 250 MPa or lower, an elongation of 30% or lower, a total light transmittance of 80% or higher, and a polar component of surface free energy of 1.5 mJ / m 2 ~10mJ / m 2 , comprising a structural unit represented by the following general formula (1).
[0073] [Chemistry 1]
[0074]
[0075] X in formula (1) is selected from
[0076] [Chemistry 2]
[0077]
[0078] At least one alicyclic group in the group consisting of
[0079] Y is the choice of
[0080] [Chemistry 3]
[0081]
[0082] At least one aromatic group in the group consisting of.
[0083] The polyimide film 2 of this embodiment can be used in a film state, and can also be obtained as follows: a varnish of polyamic acid represented by the general formula (2) which is a starting material of polyimide is applied on the surface of a planar support 1 or the surface of a three-dimensional support 1', and the organic solvent contained in the varnish is removed by heating at 280°C to 320°C to carry out dehydration and cyclization reactions of the polyamic acid.
[0084] [Chemistry 4]
[0085]
[0086] The varnish of the polyamic acid represented by the general formula (2) can be obtained by reacting an alicyclic diamine compound with tetracarboxylic dianhydride in an organic solvent.
[0087] Preferably, the diamine compound used as the starting material of the polyamic acid of the general formula (2) is selected from 2,5-diaminomethyl-bicyclo[2,2,1]heptane, 2,6-diaminomethyl-bicyclo[2,2,1]heptane, 1,4-cyclohexanediamine, and 1,4-bis(aminomethyl)cyclohexane, and the tetracarboxylic dianhydride is selected from pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride. When these diamine compounds are used, X in the formula (1) is at least one alicyclic group selected from the group consisting of the following structures.
[0088] [Chemistry 5]
[0089]
[0090] When the diamine compound used as the starting material of the general formula (2) is 2,5-diaminomethyl-bicyclo[2,2,1]heptane, 2,5-diexo-diaminomethyl-bicyclo[2,2,1]heptane, 2-endo-5-exo-diaminomethyl-bicyclo[2,2,1]heptane, and 2,5-diendo-diaminomethyl-bicyclo[2,2,1]heptane are examples of stereoisomers. When the diamine compound is 2,6-diaminomethyl-bicyclo[2,2,1]heptane, 2,6-diexo-diaminomethyl-bicyclo[2,2,1]heptane are examples of stereoisomers. Bicyclo[2,2,1]heptane, 2-endo-6-exo-diaminomethyl-bicyclo[2,2,1]heptane, 2,6-diendo-diaminomethyl-bicyclo[2,2,1]heptane as stereoisomers, in the case of 1,4-cyclohexanediamine, cis-1,4-cyclohexanediamine, trans-1,4-cyclohexanediamine as stereoisomers, in the case of 1,4-bis(aminomethyl)cyclohexane, cis-1,4-bis(aminomethyl)cyclohexane, trans-1,4-bis(aminomethyl)cyclohexane as stereoisomers. In addition, these isomers may be used alone or as a mixture.
[0091] In addition, as the diamine compound, for example, cyclobutanediamine, cyclohexanediamine, di(aminomethyl)cyclohexane, diaminobicycloheptane, diaminomethylbicycloheptane (including norbornanediamines such as norbornanediamine), diaminooxybicycloheptane, diaminomethoxybicycloheptane (including oxanorbornanediamine), isophoronediamine, diaminotricyclodecane, diaminomethyltricyclodecane, bis(aminocyclohexyl)methane [or methylenebis(cyclohexylamine)], bis(aminocyclohexyl)isopropylidene, etc. can also be used. In addition, the structure may have a substituent that is relatively stable in an environment such as heat, air, water, light, humidity, etc.
[0092] In addition, as the tetracarboxylic dianhydride, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(3,4-dicarboxyphenyl)sulfide dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,3,6,7-naphthalenetetracarboxylic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 2,2',3,3'-benzophenonetetracarboxylic anhydride, 2,2',3,3'-biphenyltetracarboxylic anhydride, 2,2-bis(2,3 -dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, bis(2,3-dicarboxyphenyl) ether dianhydride, bis(2,3-dicarboxyphenyl) sulfide dianhydride, bis(2,3-dicarboxyphenyl) sulfone dianhydride, 1,3-bis(2,3-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(2,3-dicarboxyphenoxy)phthalic anhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxybenzoyl)phthalic anhydride, 1, 4-bis(3,4-dicarboxybenzoyl)phthalic anhydride, 1,3-bis(2,3-dicarboxybenzoyl)phthalic anhydride, 1,4-bis(2,3-dicarboxybenzoyl)phthalic anhydride, 4,4'-oxydiphthalic anhydride, diazonium diphenylmethane-2,2',3,3'-tetracarboxylic anhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)-tetrahydronaphthalene-1,2-dicarboxylic anhydride, 3,3,4,4-dicyclohexyltetracarboxylic anhydride, etc. In addition, the structure may have a substituent that is relatively stable in an environment such as heat, air, water, light or humidity.
[0093] The organic solvent used when the polyamic acid of the general formula (2) is produced in the varnish is not particularly limited as long as it is a solvent that can dissolve the diamine and the tetracarboxylic dianhydride. Examples thereof include phenolic solvents such as phenol, o-chlorophenol, m-chlorophenol, p-chlorophenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, and 3,5-xylenol; and non-phenolic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylacetamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, and hexamethylphosphoric triamide. Protic or amide solvents based thereon; 1,2-dimethoxyethane, bis(2-methoxyethyl) ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl] ether, 1,4-dioxane, 2-methoxyethanol, 2-ethoxyethanol, 2-(methoxymethoxy)ethoxyethanol, 2-isopropoxyethanol, 2-butoxyethanol, tetrahydrofurfuryl alcohol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monoethyl ether, tetraethylene glycol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, Ether solvents such as tripropylene glycol monomethyl ether, polyethylene glycol, polypropylene glycol, and diethylene glycol diethyl ether; amine solvents such as pyridine, quinoline, isoquinoline, α-methylpyridine, β-methylpyridine, γ-methylpyridine, isophorone, piperidine, 2,4-lutidine, 2,6-lutidine, trimethylamine, triethylamine, tripropylamine, and tributylamine; water-soluble alcohol solvents such as methanol, ethanol, 1-propanol, 2-propanol, tert-butanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-butene-1,4-diol, 2-methyl-2,4-pentanediol, 1,2,6-hexanetriol, and diacetone alcohol; dimethyl Sulfoxide, dimethyl sulfone, diphenyl ether, sulfolane, diphenyl sulfone, tetramethyl urea, anisole, benzene, toluene, o-xylene, m-xylene, p-xylene, chlorobenzene, o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, bromobenzene, o-dibromobenzene, m-dibromobenzene, p-dibromobenzene, o-chlorotoluene, m-chlorotoluene, p-chlorotoluene, o-bromotoluene, m-bromotoluene, p-bromotoluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, γ-butyrolactone, pentane, hexane, heptane, cyclohexane, methylene chloride, chloroform, carbon tetrachloride, fluorobenzene, methyl acetate, ethyl acetate, butyl acetate, methyl formate, ethyl formate and other solvents may be used alone or in combination of two or more.
[0094] Among the above solvents, aprotic solvents or amide solvents based thereon are preferred, and N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylacetamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, and hexamethylphosphoric triamide are more preferred.
[0095] If the tensile strength of the formed polyimide film 2 exceeds 250 MPa, the hardness of the film becomes significant and the softness is not appropriate. In addition, the tensile strength is correlated with the glass transition temperature. From the perspective of the tensile strength, the glass transition temperature needs to be set to 310°C or less. In addition, if the film is easily elongated, the shape of the printed formation such as the electrode cannot be maintained, so the elongation needs to be set to 30% or less. In order to make the configuration location of the tactile sensor inconspicuous, the total light transmittance needs to be 80% or more.
[0096] The film thickness of the polyimide film 2 of the present embodiment is 1 μm to 500 μm, preferably 1 μm to 350 μm, and more preferably 1 μm to 100 μm.
[0097] The first electrode 3 formed on the polyimide film 2 of the present embodiment can be formed by drawing metal particle ink, metal paste, conductive carbon material, conductive polymer material, or conductive organic compound using a printing technique and firing the resultant.
[0098] Specifically, as metal particle inks and metal pastes, for example, metal particles of gold, silver, copper, nickel, zinc, aluminum, calcium, magnesium, iron, platinum, palladium, tin, chromium, lead, etc., metal alloys of these metals such as silver / palladium, silver oxide, organic silver, organic gold, etc., which are thermally decomposable metal compounds that provide conductive metals by thermal decomposition at relatively low temperatures, and metal oxide particles such as zinc oxide (ZnO) and indium tin oxide (ITO), etc. can be used. In particular, gold, silver, and copper metals can be preferably used. The volume resistivity thereof varies depending on the type of metal used and the heating and calcining temperature conditions, and is preferably 1.0×10 -6 Ω·cm~1.0×10 -2 Ω·cm.
[0099] Furthermore, as conductive carbon materials, there are conductive carbon compounds such as graphite, acetylene black, furnace black, thermal black, graphite, and carbon nanotubes. The volume resistivity thereof varies depending on the type of material used and the heating and calcining temperature conditions. For example, it is preferably 1.0×10 -3Ω·cm~10Ω·cm. As the conductive polymer material, for example, there can be listed: polythiophene, polyethylene dioxythiophene / polystyrene sulfonic acid (hereinafter referred to as PEDOT / PSS), polyaniline, polypyrrole, polyacetylene, polyparaphenylene, polyparaphenylene vinylene, or conjugated organic compounds such as their derivatives. The volume resistivity varies depending on the type of material used, the concentration of the dopant, and the heating and calcining temperature conditions. For example, it is preferably 1.0×10 -5 Ω·cm~1.0×10 2 Ω·cm.
[0100] As metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound, known substances can also be used. Their viscosity at room temperature (25° C.) is, for example, in the range of 0.001 Pa·s to 1200 Pa·s. Preferably, it is 1 Pa·s to 500 Pa·s. The viscosity can be adjusted using a solvent.
[0101] The solvent is not particularly limited, and examples thereof include: alcohols such as methanol, ethanol, and butanol, ethers such as tetrahydrofuran, diethyl ether, dibutyl ether, dimethoxyethane, or dioxane, aromatic cyclic hydrocarbons such as benzene, toluene, xylene, or ethylbenzene, aliphatic hydrocarbons such as pentane, hexane, or heptane, aliphatic cyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, or decahydronaphthalene, halogenated hydrocarbons such as dichloromethane, dichloroethane, dichloroethylene, tetrachloroethane, chlorobenzene, or trichlorobenzene, esters such as methyl acetate or ethyl acetate, etc. These may be used alone or in combination of two or more.
[0102] Furthermore, in addition to these, a leveling agent may be used in combination, and a polymer compound may be contained to supplement the functions of the metal particle ink, metal paste, conductive carbon material, conductive polymer material, and conductive organic compound. Although not particularly limited, for example, acrylic resin, epoxy resin, etc. may be mixed in order to impart adhesion and adjust elasticity.
[0103] In addition, although it is not necessary in all cases, when the finally manufactured tactile sensor is peeled off from the three-dimensional support body 1' and attached to another three-dimensional object having the same Gaussian curvature, a large stress is sometimes applied to the sensor. In order to alleviate the stress, a metal paste added with an elastomer (hereinafter referred to as a stretchable conductive paste) may also be used.
[0104] The first electrode 3 of this embodiment can be set to an inconspicuous size in order to be present on the surface of the plane or three-dimensional object to be finally mounted in an inconspicuous state. That is, by reducing the size of the electrode as much as possible and arranging it in an array at a certain density, the device can be made inconspicuous. The area of the electrode is not particularly limited, but the area of one electrode is 5.0×10 -3 cm 2 ~25cm 2 The range is preferably 1.0×10 -2 cm 2 ~15cm 2 In addition, the shape is not particularly limited, but preferably a triangle, a quadrilateral, a pentagon, a hexagon, a circle, an ellipse, or a combination of these shapes.
[0105] As a printing method for applying the metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste of this embodiment as the first electrode 3 on the polyimide film 2 on the planar support 1, there can be listed: soft rubber gravure offset printing, inkjet printing, dispenser, screen printing, gravure offset printing, flexographic printing, letterpress reverse printing, spin coating, spray coating, blade coating, dip coating, cast coating, roller coating, rod coating, die coating, etc., and the various electrode materials can be used according to each printing method. On the other hand, as a coating on a Gaussian curvature having an absolute value of 0.04cm -2 The following methods for printing on the polyimide film 2 on the curved three-dimensional support 1' include: soft rubber blanket gravure offset printing, inkjet printing that can be printed on three-dimensional objects, dispensers that can be applied to three-dimensional objects, etc. In the case of using soft rubber blanket gravure offset printing, the soft rubber blanket mostly uses rubber such as polydimethylsiloxane (hereinafter referred to as PDMS) with low surface free energy and lipophilicity. Therefore, it is preferred to use metal particle ink containing hydrocarbon organic solvents, metal paste, conductive polymer materials mainly containing alcohol solvents, or stretchable conductive paste.
[0106] By using these printing methods, the metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste can be directly applied to the polyimide film 2 to draw the first electrode 3. After that, a laminated body having the first electrode 3 formed thereon by calcination can be made. The calcination can be performed in the atmosphere or in an inert gas such as nitrogen or a rare gas. At this time, the laminated body can be printed and / or calcined in advance on a hard and smooth surface table or plate such as glass, stainless steel, or highly heat-resistant plastic, by fixing with a heat-resistant belt, vacuum suction, or heating and bonding.
[0107] The calcination temperature is 80°C to 200°C, preferably 80°C to 180°C, and more preferably 80°C to 160°C. This allows a uniform and strong bonding or welding interface to be formed at the interface between the polyimide film 2 and the calcined first electrode 3. The calcination of the first electrode 3 using metal particle ink or metal paste can be performed using a photocalcination method using a xenon flash lamp, a heating calcination method using an oven or a plate using an infrared heater, and the like. The thickness of the first electrode 3 thus formed is preferably in the range of 100nm to 1000μm, more preferably 500nm to 100μm, and more preferably 500nm to 10μm.
[0108] The ferroelectric layer 4 of the present embodiment uses a vinylidene fluoride polymer and a copolymer with vinylidene fluoride and trifluoroethylene as constituent units, but is not limited to this. The copolymer containing fluorine atoms using these constituent units has three types of crystal structures, namely, α-type, β-type, and γ-type, among which only the β-type crystal structure has the property of high dielectric constant and ferroelectricity due to the orientation polarization caused by the application of an electric field. This ferroelectricity is related to the manifestation of piezoelectricity and can be used as a tactile sensor, so it is important to effectively obtain the β-type crystal structure. Polyvinylidene fluoride using vinylidene fluoride as a single monomer usually adopts the α-type, which needs to be converted into the β-type by uniaxial stretching, and requires large-scale equipment for stretching and forming. On the other hand, the copolymer of vinylidene fluoride and trifluoroethylene can easily form a β-type crystal structure by using a solution printing method. If the treatment as a solution is considered, a copolymer with vinylidene fluoride and trifluoroethylene as constituent units can be preferably used.
[0109] In particular, when the molar ratio of vinylidene fluoride / trifluoroethylene is high, the residual polarization when an electric field is applied is large, and as a result, the ability to convert a small deformation into a voltage signal, i.e., the piezoelectricity is excellent. From the viewpoint of the preferential formation of the β-type crystalline structure and the manifestation of high piezoelectricity, it is preferred to use a vinylidene fluoride / trifluoroethylene copolymer (hereinafter referred to as P(VDF-TrFE)) with a molar ratio of vinylidene fluoride / trifluoroethylene of 95 / 5 to 50 / 50, more preferably a molar ratio of 90 / 10 to 70 / 30, and further preferably a molar ratio of 80 / 20 to 70 / 30.
[0110] Furthermore, the method for forming the P (VDF-TrFE) layer of the ferroelectric layer 4 is preferably a method of dissolving the copolymer in an organic solvent to form a varnish. The method of applying the varnish is not particularly limited, and the printing method for applying it on the first electrode 3 of the stacked body formed on the planar support 1 includes: soft rubber gravure offset printing, inkjet printing, dispenser, screen printing, gravure offset printing, flexographic printing, letterpress reverse printing, spin coating, spray coating, blade coating, dip coating, cast coating, roller coating, rod coating, die coating, etc. On the other hand, the printing method for applying it on the first electrode 3 of the stacked body formed on the three-dimensional support 1' includes soft rubber gravure offset printing, inkjet printing that can be printed on a three-dimensional object, a dispenser that can be applied to a three-dimensional object, and drop coating.
[0111] There is no particular limitation on the type and combination of organic solvents used when forming the P (VDF-TrFE) layer of the ferroelectric layer 4. Examples thereof include toluene, xylene, mesitylene, decahydronaphthalene, N-methyl-2-pyrrolidone, anisole, γ-butyrolactone, chlorobenzene, dichlorobenzene, trichlorobenzene, tetrahydronaphthalene, 1-methylnaphthalene, 1,4-diisopropylbenzene, diethylene glycol monobutyl ether, propylene glycol 1-monomethyl ether 2-acetate, butyl acetate, ethanol, butanol, etc. After printing, the solvent is removed by heating the coating film, and P (VDF-TrFE) mainly forms a β-type crystalline structure. However, in order to form a P (VDF-TrFE) layer with a β-type crystalline structure, it is necessary to eliminate the initial polarization by heating the copolymer to a temperature at which polarization disappears, that is, a temperature above the Curie temperature, and then slowly cool it to a temperature below the temperature at which it is converted into a β-type crystalline structure. The heating temperature is 50°C to 150°C, preferably 60°C to 140°C, and more preferably 90°C to 140°C.
[0112] The thickness of the ferroelectric layer 4 formed in the above manner is not particularly limited, but if it is taken into account that the orientation polarization should be promoted by applying a relatively low electric field for safety and economic reasons, the thickness is preferably 0.5μm to 15μm, and further preferably: in order to form the ferroelectric layer without defects and obtain the residual polarization by applying a low electric field, the ideal thickness is 1.0μm to 7.0μm.
[0113] After the above process, the second electrode 5 formed on the ferroelectric layer 4 can be formed by using printing technology to draw the same metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste as the first electrode 3 in a manner that the ferroelectric layer 4 is clamped in the cross-sectional direction and overlaps with the first electrode 3, and then calcining it.
[0114] As the metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste of this embodiment, known substances can be used. As with the first electrode 3, their viscosity at room temperature (25° C.) is, for example, in the range of 0.001 Pa·s to 1200 Pa·s. Preferably, it is 1 Pa·s to 500 Pa·s, and the viscosity can be adjusted using a solvent.
[0115] As with the first electrode 3, the solvent is not particularly limited, and examples thereof include: alcohols such as methanol, ethanol, and butanol, ethers such as tetrahydrofuran, diethyl ether, dibutyl ether, dimethoxyethane, or dioxane, aromatic cyclic hydrocarbons such as benzene, toluene, xylene, or ethylbenzene, aliphatic hydrocarbons such as pentane, hexane, or heptane, aliphatic cyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, or decahydronaphthalene, halogenated hydrocarbons such as dichloromethane, dichloroethane, dichloroethylene, tetrachloroethane, chlorobenzene, or trichlorobenzene, esters such as methyl acetate or ethyl acetate, etc. These may be used alone or in combination of two or more.
[0116] Furthermore, in addition to these, a leveling agent may be used in combination, and a polymer compound may be contained to supplement the functions of the metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste. Although not particularly limited, for example, acrylic resin or epoxy resin may be mixed in order to impart adhesion and adjust elasticity. As long as the viscosity is within the above range, the coating and printing method may be appropriately selected.
[0117] The area of the second electrode 5 is not particularly limited, but its area is the same as that of the first electrode 3, and the area of one electrode is 5.0×10 -3 cm 2 ~25cm 2 The range is preferably 1.0×10 -2 cm 2 ~15cm 2 In addition, its shape is not particularly limited, but is preferably a triangle, a quadrilateral, a pentagon, a hexagon, a circle, an ellipse, or the like.
[0118] As printing methods for using the metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste of this embodiment as the second electrode 5 and applying it on the ferroelectric layer 4 of the stack formed on the planar support body 1, the following methods can be listed: soft rubber gravure offset printing, inkjet printing, dispenser, screen printing, gravure offset printing, flexographic printing, letterpress reverse printing, spin coating, spray coating, blade coating, dip coating, cast coating, roller coating, rod coating, die coating, etc., and the various electrode materials can be used according to each printing method. On the other hand, as a printing method for coating the ferroelectric layer 4 of the stack formed on the three-dimensional support body 1', there can be listed soft rubber blanket gravure offset printing, inkjet printing that can be printed on a three-dimensional object, a dispenser that can be coated on a three-dimensional object, etc. In the case of using soft rubber blanket gravure offset printing, the soft rubber blanket mostly uses rubber such as PDMS with low surface free energy and lipophilicity, so it is preferred to use metal particle ink containing hydrocarbon organic solvents, metal paste, conductive polymer materials mainly containing alcohol solvents, or stretchable conductive paste.
[0119] By using these printing methods, the metal particle ink, metal paste, conductive carbon material, conductive polymer material, conductive organic compound or stretchable conductive paste can be directly applied to the ferroelectric layer 4, thereby drawing the second electrode 5. Afterwards, a stacked body having the second electrode 5 formed thereon can be produced by calcination. The calcination can be carried out in the atmosphere, or in an inactive gas such as nitrogen or a rare gas. At this time, the stacked body can be printed and / or calcined in advance on a hard and smooth surface table or plate such as glass, stainless steel, or a highly heat-resistant plastic, by fixing with a heat-resistant belt, vacuum suction, or heating and sealing.
[0120] The calcination temperature is different from that of the first electrode 3 and needs to be set to a temperature that takes into account the Curie temperature of the ferroelectric layer 4. That is, by heating at a temperature below the Curie temperature of the ferroelectric layer 4, the crystal structure of the ferroelectric does not change. The calcination temperature is 50°C to 140°C, preferably 60°C to 130°C, and more preferably 90°C to 130°C. The calcination of the second electrode 5 using metal particle ink or metal paste can be performed using a light calcination method using a xenon flash lamp, a heating calcination method using an oven or a plate using an infrared heater, etc., and the temperature is set to be within the above range. The thickness of the second electrode 5 thus formed is preferably in the range of 100nm to 1000μm, more preferably 500nm to 100μm, and further preferably 500nm to 10μm. The volume resistivity of the electrode varies depending on the material used and the calcination temperature conditions taking into account the Curie temperature, but its range is the same as that of the first electrode 3.
[0121] The ferroelectric layer 4 of this embodiment has a structure polarized in the direction of the electric field application by applying an electric field through the first electrode 3 and the second electrode 5. If the ferroelectric layer 4 and the electrodes are properly formed, a polarization-hysteresis loop (hereinafter referred to as a PE curve) is drawn to obtain the polarization amount when the electric field is zero in the curve, that is, the residual polarization. The molar ratio of vinylidene fluoride / trifluoroethylene constituting P (VDF-TrFE) is in the range of 95 / 5 to 50 / 50, depending on the crystallinity, and the residual polarization is 1μC / cm 2 ~20μC / cm 2 , preferably 2μC / cm 2 ~15μC / cm 2 , more preferably 3μC / cm 2 ~10μC / cm 2 This residual polarization helps to show the piezoelectricity that generates a voltage signal when the ferroelectric layer 4 is deformed by pressure. In the present invention, when the piezoelectricity is used and pressure is applied by a human finger, a tactile sensor that detects contact is formed. The residual polarization is 6.5μC / cm 2 ~9.0μC / cm 2 .
[0122] The tactile sensor can be used in a state of being attached to the formed plane support 1 or three-dimensional support 1', or can be peeled off from the support and attached to another plane or three-dimensional object. When attached to another plane or three-dimensional object, an adhesive or double-sided tape that can be bonded at a temperature above room temperature can be sandwiched between the polyimide film and the three-dimensional object. When attached, the plane or the three-dimensional object does not necessarily need to be heat-resistant, so it can be applied to three-dimensional objects using various raw materials such as plastic, glass, metal, paper, etc.
[0123] Furthermore, in the present embodiment, by grounding either the first electrode 3 or the second electrode 5 of the tactile sensor as a ground electrode, and connecting the first electrode 3 or the second electrode 5 facing the ground electrode to a specific electronic circuit, it is possible to control the noise received by the human body itself or from the environment, and transmit the voltage signal generated in the tactile sensor. The main factors of the noise include 50Hz or 60Hz AC commercial power supply, vibration of a plane or three-dimensional object on which the tactile sensor is installed, etc. The situation when the noise from the AC commercial power supply is superimposed on the touch is shown in FIG. Figure 2 . Figure 2In the example, the contact is sensed at the point showing the highest voltage value, and then it decays, but it is confirmed that there is noise superimposed on it from the 50Hz AC commercial power supply. The method of controlling the noise and extracting only the contact as a voltage signal is not particularly limited, and examples thereof include: a method of covering the first electrode 3 and the second electrode 5 with an electromagnetic wave shielding film (conductive material, external electrode, insulating material, etc.) to protect the first electrode 3 and the second electrode 5, a method of using a coaxial cable for wiring, a method of using various filter circuits (low-pass filter, high-pass filter, band-pass filter, etc.), a method of using a comparator, etc., and multiple such methods may also be combined.
[0124] In addition, an electronic circuit can be designed to detect even a slight pressure on the touch sensor. The method of detecting the slight pressure is not particularly limited, and an example of the method is to amplify the generated voltage using an operational amplifier. It is clear here that the surface free energy of the polyimide film 2 of this embodiment affects the performance of the touch sensor.
[0125] That is, it is learned in detail that when the metal particle ink, metal paste, conductive carbon material, conductive polymer material or conductive organic compound, or stretchable conductive paste is applied as the first electrode 3 on the polyimide film 2, and when the ferroelectric layer 4 is applied on the first electrode 3, the formation state after the heat treatment depends on the surface free energy of the polyimide film 2. This energy can be decomposed into polar components and dispersed components, and their total amount is at least 15mJ / m 2 ~80mJ / m 2 , more preferably 25mJ / m 2 ~70mJ / m 2 , particularly preferably 30 mJ / m 2 ~60mJ / m 2 . It can be calculated using the contact angles of different liquids.
[0126] In particular, in the embodiment of the present invention, as described above, the energy component that has an influence is the sum of the polar component and the dispersed component, but is more dominated by the polar component than the dispersed component. The surface free energy of the polar component is in the range of 1.5 mJ / m 2 ~10mJ / m 2 , preferably 2.0 mJ / m 2 ~8.0mJ / m 2 , more preferably 2.5 mJ / m 2 ~6.0mJ / m 2 By using an electronic circuit that can avoid noise by receiving a voltage signal from the touch sensor formed on the polyimide film 2 of the present invention, a touch sensor can be formed.
[0127] By using the tactile sensor produced as described above and the voltage signal for controlling the noise superimposed on the tactile sensor, a switch device for switching the on state and the off state of the voltage can be produced. The method is not particularly limited, and for example, various flip-flop circuits (reset-set flip-flop, delay flip-flop, and JK flip-flop produced by using these, toggle flip-flop, etc.) can be listed. From the perspective of simplifying the circuit by setting the input terminal to one and the ease of obtaining, in this embodiment, a toggle flip-flop produced by a delay flip-flop is preferred.
[0128] Regarding the manufacturing method of this embodiment, if it is clearly described as a specific example, the polyimide film 2 of this embodiment is formed into a film via a varnish of polyamic acid. That is, the diamine compound and the tetracarboxylic dianhydride are dissolved in an organic solvent such as N-methyl-2-pyrrolidone to generate polyamic acid, and then varnish is formed. In the case where the varnish is applied to the surface of a planar support 1 of borosilicate glass, for example, a scraper coater is used to apply the varnish to a surface having an absolute value of Gaussian curvature of 0.04 cm -2 The following curved surface is formed on the surface of the support 1' by a spherical surface of borosilicate glass, in this case by gravure offset printing using a soft blanket.
[0129] The coated support is calcined at 320° C. for 2 hours in a stream of an inert gas such as nitrogen or under reduced pressure to obtain the polyimide film 2. In most cases, the polyimide film 2 is attached to a planar support 1 or a three-dimensional support 1', and the first electrode 3, the ferroelectric layer 4, and the second electrode 5 are formed in this state. This is more convenient from the process point of view, but it is not limited to being used after being peeled off from the planar support 1 or the three-dimensional support 1'.
[0130] When the first electrode 3 is formed on the polyimide film 2 on the planar support 1 of the present embodiment, for example, screen printing is used, or when the first electrode is formed on the polyimide film 2 on the three-dimensional support 1', for example, soft rubber gravure offset printing is used to print an alcohol solution of PEDOT / PSS (manufactured by Heraeus), and the first electrode 3 of PEDOT / PSS with a thickness of 100nm to 1000μm is obtained by heating and calcining.
[0131] Then, on the first electrode 3, for the polyimide film 2 on the planar support 1, a varnish made by dissolving P(VDF-TrFE) in N-methyl-2-pyrrolidone is applied by a doctor blade coater, and for the polyimide film 2 on the three-dimensional support 1', a varnish made by dissolving P(VDF-TrFE) in N-methyl-2-pyrrolidone is applied on the first electrode 3 by a syringe. The solvent is evaporated by calcination at 50°C to 150°C, and a P(VDF-TrFE) layer with a thickness of 0.5μm to 15μm having a β-type crystal structure is obtained. On the P(VDF-TrFE) layer, PEDOT / PSS is coated by the same method as the first electrode, and calcination is performed at 50°C to 140°C, thereby obtaining a second electrode with a thickness of 100nm to 1000μm. By applying an electric field to the P(VDF-TrFE) via the first electrode 3 and the second electrode 5 , a structure polarized in the direction of electric field application is obtained, thereby exhibiting piezoelectricity and obtaining a tactile sensor.
[0132] Here, as a method of controlling noise from the outside world mixed with the contact pressure, an active filter using an operational amplifier with built-in active elements such as transistors is preferred over a passive filter using only passive elements such as resistors and capacitors. Figure 3 The passive low-pass filter shown is Figure 4 The characteristics of the active Sallen-Key low-pass filter shown in Figure 1 are compared. A voltage with a frequency range of 100mHz to 100Hz is input to Figure 3 and Figure 4 For each circuit, find the gain shown in the following equation.
[0133] [Formula 1]
[0134]
[0135] If you observe Figure 3 and Figure 4 The frequency dependence of the gain is known. Figure 4 The active Sallen-Key low-pass filter has a significantly reduced gain at frequencies above 50 Hz, so that noise above this frequency is attenuated by the filter. As a result, only contact with an object can be sensed specifically. In addition, the active low-pass filter is not limited to Figure 4 The Sallen-Key low-pass filter shown may also be constituted by an appropriate active low-pass filter according to the state of noise generation.
[0136] The active filter is a noise control method based on the so-called analog electronic circuit. In addition, only high or low digital circuits can also be used as a noise control method. Specifically, if the voltage signal generated by the tactile sensor is amplified by an operational amplifier, the mixed noise is also amplified. However, if a comparator as a digital circuit is connected, the voltage generated by the tactile sensor can be turned on and the noise can be turned off. Furthermore, it is confirmed that as shown in the embodiment, by setting Figure 6 The two-state trigger in the switch function can be obtained. As a result, by Figure 7 The touch sensor is shown to switch the voltage between the on and off states by touching the touch sensor with a finger. In order to visually understand the situation easily, a switching device is implemented to switch between the on and off states of the voltage applied to the LED and / or oscillator in response to the touch pressure of the finger.
[0137] In addition, the on and off states of the voltage can be recognized not only by vision but also by other senses such as touch and hearing. That is, the switch device of this embodiment can have a recognition unit (LED, speaker, etc.) that recognizes the on and off states of the voltage by sense.
[0138] As a comparative example, it can be seen that in an electronic circuit ( Figure 8 ), the noise is also amplified along with the touch of the finger, so the on and off states of the voltage behind the two-state touch trigger become unstable and cannot be switched normally ( Fig. 9 ).
[0139] In this embodiment, the pressure detected by the tactile sensor is converted into a voltage signal, which switches the on and off states of the electronic circuit. As a result, light emitters such as LEDs and organic ELs, and oscillators (vibrators) operate and can drive other devices at the same time. For example, the on and off states of the mechanical movements of a robot can be switched. The pressure converted into the voltage signal can be turned on and off even if it is touched lightly and gently with a finger. The biggest reason is that the polar component of the surface free energy is 1.5mJ / m 2 ~10mJ / m 2 The electrode, ferroelectric, and electrode are sequentially formed on the polyimide film with high total light transmittance represented by the general formula (1), so that while maintaining the shape of the sensor, the sensor component as a transparent electronic device can respond even to a weak voltage signal. In addition, the thickness of the sensor is 5μm to 100μm, preferably 5μm to 50μm, and more preferably 5μm to 10μm.
[0140] Furthermore, if the polyimide film is used as a substrate, poor electrode formation will not occur when the conductive ink or paste is printed and calcined, and the defective rate of electronic device products required by the market can be achieved below 0.1%. From the perspective of protecting consumers' economy, ensuring quality, and preventing accidents, the yield rate of the preferred product can reach more than 99.9%.
[0141] The voltage signal of the tactile sensor and the information on the on and off states of the switching device obtained in the described manner are then digitized through analog-to-digital conversion and sent to a computer via wireless communication, thereby remotely grasping the information. When the sensor is installed on the surface of a robot, for example, it can be used to drive a mechanism to avoid strong collisions between the robot and the human body that the sensor contacts.
[0142] In addition, in order to read the measurement results using the software, it is preferred to use the wireless function of digital terminals such as smartphones, smart watches, and tablet terminals with communication functions that have become widely popular in recent years, but of course USB cables or socket cables can also be used for transmission, and there is no limit to the use of both.
[0143] These communication functions can also utilize wireless communication called Near Field Communication (NFC) using a frequency of 13.56MHz that can be used for wireless power supply, and wireless communication of international standards such as ISO / IEC 14443, ISO / IEC 18092, ISO / IEC 15693, ISO / IEC 21481 can be used to make so-called passive electronic devices. In addition, as an IC tag with these communication functions, an information function can be carried to make it have the function of RFID. It can also be made into an active electronic device with a battery mounted thereon. Furthermore, although it is necessary to carry a primary battery or a secondary battery or a wiring power supply, it is also possible to utilize Bluetooth basic rate / enhanced data rate or Bluetooth low energy (~5m) available at 2.4GHz frequency or UHF or ZigBee (ZigBee) of 2.4GHz band, 900MHz band (e.g., 920MHz (~100m)) and 800MHz band. Furthermore, the 0.7 GHz to 2.0 GHz band of the 4G communication band, the 3.0 GHz to 4.1 GHz band of the 5G Sub6 band, the 27.00 GHz to 29.50 GHz band of the 5G millimeter wave band, etc. can also be used.
[0144] In order to have the above-mentioned information communication function, a transceiver antenna for information communication can be formed on the touch sensor of this embodiment by a coating printing technique, thereby providing a bendable or stretchable electronic device using the same.
[0145] In order to provide a sensor device economically and inexpensively, the tactile sensor is equipped with a device that utilizes various existing inexpensive integrated circuits (ICs) and resistors for controlling voltage, and temporarily replaces the physical quantity of information from the sensor with an electrical signal as described above so that the electronic circuit can process it, and then reconverts it so that it can be recognized by humans. The signal obtained by the electrical circuit can be converted using an AD converter that replaces the analog signal with a digital signal so that humans can read the measurement result using software.
[0146] In this embodiment, it is necessary to install in the above-mentioned tactile sensor in an economical and inexpensive method and in a durable method: integrated circuits (ICs) such as CMOS for rectification or signal conversion, AD conversion circuits or noise reduction circuits, resistors, amplifiers, lasers, light emitters such as organic EL or LED lights, NFC, Bluetooth, Wi-SUN, UHF or ZigBee communicators, and various electronic parts or connecting wiring. As a method for its installation, solder is generally a cheap material, and low-temperature curing flexible conductive adhesives can also be used. Although it is true that the cost is increasing now, it may be an economical material in the future.
[0147] Regarding the method of soldering here, it can be performed by manual operation of the solder wire using a soldering iron, but the flow method or the reflow method is a commonly used method in industry. In this embodiment, any method can be selected, but in industry, it is preferred to use the following method to install electronic components or connect wiring, the method is: on the printed substrate, the solder paste is squeegee-printed using a screen such as a stainless steel metal shield with holes in the part where the electronic components are installed, and the components are placed on it and heated to melt the solder. After installing the electronic components or connecting the wiring, the tactile sensor substrate formed in this embodiment and the installed electronic components can also be preheated in a reflow furnace before formal heating to avoid rapid thermal shock to the components or to activate the flux, vaporize the solvent, etc. In this embodiment, the preheating temperature is in the range of 100°C to 150°C, and the formal heating can be performed at 140°C to 180°C and the heating time is short. Furthermore, cooling can be natural cooling, but in order to avoid thermal stress of electronic components or to prevent peeling and cracking of solder, rapid cooling can also be performed. Furthermore, instead of printing, solder balls may be added to the IC and placed on the mounting portion for reflow.
[0148] [Example]
[0149] The present invention will be specifically described below using examples, but the present invention is not limited thereto. The defective rate of the tactile sensor here means that the average residual polarization of the tactile sensor produced through all the steps does not show 7.0 μC / cm 2The yield rate of the sensor is 10 times, and the defective rate is the value obtained by evaluating ten times.
[0150] The glass transition temperature was measured by thermomechanical analysis (TMA method). The temperature of the polyimide film was raised from 25° C., and the point at which the linear expansion coefficient changed was defined as the glass transition temperature.
[0151] Method for measuring tensile strength and elongation: The polyimide film was stretched using the ASTM D638 method, a tensile test method for plastics. The maximum stress observed in the test was taken as the tensile strength, and the strain corresponding to the stress was taken as the elongation.
[0152] Method for measuring total light transmittance: A polyimide film is formed on a flat glass plate under the same printing conditions as those for a polyimide film formed on a curved surface by soft rubber gravure offset printing. With the glass plate as the background, visible ultraviolet light is irradiated in the wavelength range of 300nm to 800nm using a visible ultraviolet spectrophotometer, and the light transmittance at each wavelength is calculated from the ratio of the incident light to the transmitted light, and the average value in the wavelength range of 450nm to 800nm is taken as the total light transmittance.
[0153] Method for measuring the thickness of the electrode: The same electrode as the electrode formed on the curved surface is printed on the flat polyimide film according to one embodiment of the present invention under the same printing conditions as the printing method used when forming the electrode on the curved surface (soft rubber gravure offset printing, inkjet printing that can be printed on a three-dimensional object, dispenser that can be printed on a three-dimensional object, etc.), and heated and calcined. The calcined electrode is scanned on the surface of the polyimide film and the surface of the electrode using a Dektak (registered trademark) stylus profiling system, and the average value of the height difference is used as the thickness of the electrode.
[0154] Volume resistivity determination method: The resistance value (R) is determined by a two-terminal determination method using a method in which the terminals are brought into contact with both ends of an electrode formed into a rectangular parallelepiped. The volume resistivity (ρ) is calculated using the following formula based on the length (L) between the two terminals and the cross-sectional area (A). In addition, when calculating the cross-sectional area (A), the thickness is the value obtained by measuring the thickness of the electrode.
[0155] [Formula 2]
[0156]
[0157] Method for determining Curie temperature: Accurately weigh 2 mg to 5 mg of powder of vinylidene fluoride / trifluoroethylene copolymer on an aluminum pan, and use a differential scanning calorimeter (DSC) to heat from 20°C to 200°C at a heating rate of 5°C / min. Then cool from 200°C to 20°C at a cooling rate of 5°C / min, and measure the endothermic and exothermic heat generated by the state change of the copolymer powder during a series of temperature changes. During the heating process, the copolymer reaches a melting point at about 140°C to 160°C and becomes a liquid. At this time, a peak caused by endothermic heat is confirmed. In the subsequent cooling process, an exothermic peak is confirmed at about 90°C to 140°C, which is lower than the melting point, and the temperature at the peak is taken as the Curie temperature.
[0158] [Example 1]
[0159] The glass transition temperature is 280°C, the tensile strength is 190 MPa, the elongation is 15%, the total light transmittance is 88%, and the total surface free energy calculated from the contact angle of water and diiodomethane is 43.2 mJ / m 2 , the polar component is 2.7mJ / m 2 Polyimide film (trade name Ecrios (registered trademark) VICT-C, manufactured by Mitsui Chemicals, Inc.) (Gaussian curvature 0 cm -2 ) was fixed on a flat support of alkali glass, and a water / alcohol solution of a conductive polymer material PEDOT / PSS (manufactured by Heraeus) was smoothly coated by screen printing using a circular screen with a diameter of 1 cm, and then calcined at 150°C for 30 minutes to evaporate the water / alcohol, thereby forming a circular surface with a diameter of 1 cm (area of 0.79 cm 2 ) The thickness of the electrode is 2.0 μm, and the volume resistivity is 4.0 Ω·cm.
[0160] Next, a 12 wt% solution of N-methyl-2-pyrrolidone of Piezotech FC25 (manufactured by Arkema) as P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25 was smoothly applied on the film by a knife coater, and the film was calcined at 135°C for 2 hours to evaporate N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm. In addition, the Curie temperature obtained by DSC measurement of Piezotech FC25 was confirmed to be 130°C.
[0161] Furthermore, a water / alcohol solution of PEDOT / PSS (manufactured by Heraeus) was smoothly applied on the ferroelectric layer by screen printing, and calcined at 125°C for 1 hour to evaporate the water / alcohol, thereby forming a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction of the ferroelectric layer.2 ) and a second electrode with a thickness of 2.0 μm.
[0162] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluating the residual polarization of the ferroelectric layer, the defective rate of the tactile sensor was 0%, that is, the good rate was 100%.
[0163] The laminate obtained above is used as a tactile sensor, and an operational amplifier and a comparator are connected to Figure 6 The touch sensor connects a red LED to a two-state touch trigger made of a delay-trigger. When the touch sensor is touched with a finger, the LED becomes on (lit), and when it is touched again, the LED becomes off (extinguished). Figure 7 It shows the generation of a voltage signal when a finger touches the touch sensor, and the voltage after the two-state touch trigger, that is, the voltage applied to the LED, is turned on and maintained in this state and switched to the off state when touched again.
[0164] Furthermore, an oscillator of FA-130RA (rated voltage 1.5V) manufactured by Mabuchi Motor was connected in parallel to the LED terminal of the manufactured touch sensor. When the touch sensor was touched with a finger, the red LED lit up and the oscillator was driven. When the finger was touched again, the LED turned off and the oscillator stopped, confirming that it was a switching device with the function of driving other devices.
[0165] [Example 2]
[0166] In the same manner as in Example 1, the conductive polymer material solution of Example 1 was evenly applied to the polyimide film (Gaussian curvature 0 cm) used in Example 1 by screen printing. -2 ) and calcined to form a circular shape with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 2.0 μm.
[0167] Next, as in Example 1, a 12 wt% solution of N-methyl-2-pyrrolidone of Piezotech FC20 (manufactured by Arkema) as P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 80:20 was smoothly applied to the laminate using a knife coater, and the laminate was calcined at 145°C for 2 hours to evaporate N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm. In addition, the Curie temperature obtained by DSC measurement of Piezotech FC20 was confirmed to be 140°C.
[0168] Furthermore, the same conductive polymer material solution as above is evenly applied on the ferroelectric layer by the same screen printing and calcined at 135°C for 30 minutes, thereby forming a second electrode with a diameter of 1 cm and a thickness of 2.0 μm, which overlaps with the first electrode in the thickness direction and sandwiches the ferroelectric layer.
[0169] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluating the residual polarization of the ferroelectric layer, the defective rate of the tactile sensor was 0%, that is, the good rate was 100%.
[0170] The stacked body obtained above is used as a tactile sensor, an operational amplifier and a comparator are connected to the tactile sensor, and a red LED is connected to a two-state touch trigger made of a delay-trigger. When the tactile sensor is touched with a finger, the LED becomes on (lit), and when it is touched again, the LED becomes off (extinguished).
[0171] [Example 3]
[0172] In the same manner as in Example 1, a solution of a conductive polymer material was evenly applied to the polyimide film (Gaussian curvature 0 cm) used in Example 1 by screen printing. -2 ), and calcined at 150° C. for 30 minutes to evaporate water / alcohol, thereby forming a first electrode with a diameter of 1 cm and a thickness of 2.0 μm.
[0173] Next, a 12 wt% solution of N-methyl-2-pyrrolidone of Piezotech FC30 (manufactured by Arkema) as P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 70:30 was smoothly applied to the laminate by a knife coater in the same manner as in Example 1, and the N-methyl-2-pyrrolidone was evaporated by calcining at 135° C. for 2 hours, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm. In addition, it was confirmed that the Curie temperature obtained by DSC measurement of Piezotech FC30 was 100° C.
[0174] Furthermore, the same conductive polymer material solution as above was evenly coated on the ferroelectric layer by screen printing, and calcined at 90°C for 1 hour, thereby forming a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction of the ferroelectric layer. 2 ) and a second electrode with a thickness of 2.0 μm.
[0175] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluating the residual polarization of the ferroelectric layer, the defective rate of the tactile sensor was 0%, that is, the good rate was 100%.
[0176] The laminate obtained above is used as a tactile sensor, and an operational amplifier and a comparator are connected to Figure 6 The touch sensor connects a red LED to a two-state touch trigger made of a delay-trigger. When the touch sensor is touched with a finger, the LED becomes on (lit), and when it is touched again, the LED becomes off (extinguished).
[0177] [Example 4]
[0178] In the same manner as in Example 1, the conductive polymer solution used in Example 1 was applied by screen printing to a glass transition temperature of 305°C, a tensile strength of 220 MPa, an elongation of 7%, a total light transmittance of 88%, and a total surface free energy value of 43.8 mJ / m 2 , the polar component is 4.7mJ / m 2 Polyimide film (trade name Ecrios (registered trademark) VICT-Cz, manufactured by Mitsui Chemicals, Inc.) (Gaussian curvature 0 cm -2 ) and calcined at 150°C for 30 minutes to evaporate the water / alcohol, thereby forming a circular shape with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 1.8 μm.
[0179] Next, as in Example 1, a 12 wt% solution of P(VDF-TrFE) in N-methyl-2-pyrrolidone with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25 is evenly coated on the laminate and calcined at 135°C for 2 hours to form a ferroelectric layer with a thickness of 3μm to 5μm.
[0180] Furthermore, a solution of the same conductive polymer material as above was evenly applied to the ferroelectric layer by screen printing and calcined at 125°C for 1 hour, thereby forming a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction sandwiching the ferroelectric layer. 2 ) and a second electrode with a thickness of 2.0 μm.
[0181] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluating the residual polarization of the ferroelectric layer, the defective rate of the tactile sensor was 0%, that is, the good rate was 100%.
[0182] The laminate obtained above is used as a tactile sensor, and an operational amplifier and a comparator are connected to Figure 6The touch sensor connects a red LED to a two-state touch trigger made of a delay-trigger. When the touch sensor is touched with a finger, the LED becomes on (lit), and when it is touched again, the LED becomes off (extinguished).
[0183] [Example 5]
[0184] In the same manner as in Example 1, the conductive polymer solution used in Example 1 was applied by screen printing to a substrate having a glass transition temperature of 265°C, a tensile strength of 130 MPa, an elongation of 18%, a total light transmittance of 90%, and a total surface free energy value of 44.0 mJ / m 2 , the polar component is 5.2mJ / m 2 Polyimide film (trade name Ecrios (registered trademark) VICT-Bnp, manufactured by Mitsui Chemicals, Inc.) (Gaussian curvature 0 cm -2 ) and calcined to form a circular shape with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 2.5 μm.
[0185] Next, in the same manner as in Example 1, a 12 wt% solution of P(VDF-TrFE) in N-methyl-2-pyrrolidone with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25 used in Example 1 is coated on the laminate, and the laminate is calcined at 135°C for 2 hours to evaporate the N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0186] Furthermore, a solution of the same conductive polymer material as above was applied to the ferroelectric layer by screen printing and calcined at 125°C for 1 hour to evaporate water / alcohol, thereby forming a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction sandwiching the ferroelectric layer. 2 ) and a second electrode with a thickness of 2 μm.
[0187] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluating the residual polarization of the ferroelectric layer, the defective rate of the tactile sensor was 0%, that is, the good rate was 100%.
[0188] The laminate obtained above is used as a tactile sensor, and an operational amplifier and a comparator are connected to Figure 6 The touch sensor connects a red LED to a two-state touch trigger made of a delay-trigger. When the touch sensor is touched with a finger, the LED becomes on (lit), and when it is touched again, the LED becomes off (extinguished).
[0189] [Example 6]
[0190] The polyimide film (Gaussian curvature 0 cm) used in Example 1 was subjected to the same method as in Example 1 except that a square screen with a side of 4 cm was used. -2 ) and a conductive polymer solution are screen printed and calcined to form a square with a side of 3.8 cm (area of 14 cm 2 ) and a first electrode with an average thickness of 2.1 μm.
[0191] Next, in the same manner as in Example 1, a 12 wt% solution of N-methyl-2-pyrrolidone of Piezotech FC25 (manufactured by Arkema), which is P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25, is coated on the laminate using a blade coater and calcined at 135°C for 2 hours to form a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0192] Furthermore, a water / alcohol solution of the same conductive polymer material as above was evenly applied to the ferroelectric layer by screen printing, and calcined at 125°C for 1 hour to form a square (area 14 cm2) with a side of 3.8 cm overlapping the first electrode in the thickness direction sandwiching the ferroelectric layer. 2 ) and a second electrode with an average thickness of 2.1 μm.
[0193] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluating the residual polarization of the ferroelectric layer, the defective rate of the tactile sensor was 0%, that is, the good rate was 100%.
[0194] The laminate obtained above is used as a tactile sensor, and an operational amplifier and a comparator are connected to Figure 6 The tactile sensor connects a red LED to a two-state touch-change trigger made of a delay-trigger. When the tactile sensor is touched with a finger, the LED becomes on (vibration state), and when it is touched again, the LED becomes off (stop state).
[0195] [Example 7]
[0196] The LED terminal of the switch device manufactured in Examples 2 to 6 was connected in parallel to an oscillator of FA-130RA (rated voltage 1.5V) manufactured by Mabuchi Motor. It was confirmed that when the touch sensor was touched with a finger, the red LED was lit and the oscillator was driven, and when the finger was touched again, the LED was turned off and the oscillator was stopped. Therefore, it was confirmed that these switch devices have the function of driving other devices.
[0197] [Comparative Example 1]
[0198] As in Example 1, a water / alcohol solution of the conductive polymer material PEDOT / PSS (manufactured by Heraeus) used in Example 1 was smoothly applied by screen printing on a glass transition temperature of 118°C, a tensile strength of 110 MPa, an elongation of 65%, a total light transmittance of 87%, and a total surface free energy value of 40.5 mJ / m 2 , the polar component is 0.92mJ / m 2 PEN (trade name Teonex (registered trademark), manufactured by Teijin Film Solutions Co., Ltd.) film (Gaussian curvature 0cm -2 ) and calcined to form a circular shape with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 2.0 μm.
[0199] Next, as in Example 1, a 12 wt% solution of P(VDF-TrFE) in N-methyl-2-pyrrolidone used in Example 1 was smoothly coated on the laminate using a blade coater and calcined at 135°C for 2 hours to form a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0200] Furthermore, a water / alcohol solution of the same conductive polymer material as above was smoothly applied to the ferroelectric layer by screen printing and calcined at 125°C for 1 hour to form a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction of the ferroelectric layer. 2 ) and a second electrode with a thickness of 2.0 μm.
[0201] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the residual polarization of the ferroelectric layer was evaluated. As a result, the defective rate of the tactile sensor was 50%, that is, the good rate was 50%.
[0202] An operational amplifier and a comparator are connected to a tactile sensor of a good product, and a red LED is connected to a two-state touch trigger made of a delay-trigger. When the tactile sensor is touched with a finger, the LED becomes on (lit), and when it is touched again, the LED becomes off (extinguished) to show the switch function. However, the red LED does not light up in the defective product.
[0203] [Comparative Example 2]
[0204] In the same manner as in Example 1, a water / alcohol solution of the conductive polymer material PEDOT / PSS (manufactured by Heraeus) used in Example 1 was smoothly applied by screen printing on a surface of the substrate having a glass transition temperature of 410°C, a tensile strength of 330 MPa, an elongation of 80%, and a total surface free energy value of 57.1 mJ / m 2 , the polar component is 36mJ / m 2 Brown (total light transmittance 50% or less) polyimide film (trade name Kapton (registered trademark), manufactured by DuPont Toray Co., Ltd.) (Gaussian curvature 0 cm -2 ) and calcined to form a circular shape with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 2.1 μm.
[0205] Next, a 12 wt% solution of P(VDF-TrFE) in N-methyl-2-pyrrolidone used in Example 1 was evenly coated on the laminate using a knife coater and calcined at 135°C for 2 hours to form a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0206] Furthermore, a water / alcohol solution of the same conductive polymer material as above was smoothly applied to the ferroelectric layer by screen printing, and calcined at 125°C for 1 hour to evaporate the solvent, thereby forming a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction sandwiching the ferroelectric layer. 2 ) and a second electrode with a thickness of 2 μm.
[0207] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the residual polarization of the ferroelectric layer was evaluated. As a result, the defective rate of the tactile sensor was 67%, that is, the good rate was 33%.
[0208] [Comparative Example 3]
[0209] As in Example 1, the water / alcohol solution of the conductive polymer material used in Example 1 was smoothly applied by screen printing on a glass transition temperature of 355°C, a tensile strength of 360 MPa, an elongation of 50%, and a total value of surface free energy of 44.6 mJ / m 2 , the polar component is 15.6mJ / m 2 Brown (total light transmittance 50% or less) polyimide film (trade name Upilex (registered trademark), manufactured by Ube Industries, Ltd.) (Gaussian curvature 0 cm -2 ) and calcined to form a circular shape with a diameter of 1 cm (area of 0.79 cm2 ) and a first electrode with a thickness of 1.8 μm.
[0210] Next, as in Example 1, a 12 wt% solution of P(VDF-TrFE) in N-methyl-2-pyrrolidone used in Example 1 was smoothly coated on the laminate using a blade coater and calcined at 135°C for 2 hours to form a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0211] Furthermore, a water / alcohol solution of the same conductive polymer material as above was smoothly applied to the ferroelectric layer by screen printing, and calcined at 125°C for 1 hour to form a circular shape (area 0.79 cm2) with a diameter of 1 cm and overlapping with the first electrode in the thickness direction sandwiching the ferroelectric layer. 2 ) and a second electrode with a thickness of 1 μm to 2 μm.
[0212] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode to obtain a PE curve and evaluate the remanent polarization of the ferroelectric layer, the defective rate of the tactile sensor was 89%, that is, the good rate was 11%.
[0213] [Comparative Example 4]
[0214] By screen printing, a water / alcohol solution of the same conductive polymer material as in Example 1 was applied to a glass transition temperature of 75°C, a tensile strength of 215 MPa, an elongation of 170%, a total light transmittance of 85%, and a total value of surface free energy of 44.0 mJ / m 2 , the polar component is 2.0mJ / m 2 PET (trade name Lumirror (registered trademark), manufactured by Toray Industries, Ltd.) (Gaussian curvature 0 cm -2 ) and calcined at 150°C for 30 minutes to form a circular shape with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 2 μm, but it caused shrinkage and wrinkles, and a smooth electrode could not be made.
[0215] [Comparative Example 5]
[0216] As in Comparative Example 4, the PET film used in Comparative Example 4 and the solution of the conductive polymer material were coated by screen printing and calcined at a calcination temperature of 100° C. for 5 hours to form a circular film with a diameter of 1 cm (area of 0.79 cm 2 ) and a first electrode with a thickness of 2 μm.
[0217] Next, as in Example 1, a 12 wt% solution of P(VDF-TrFE) in N-methyl-2-pyrrolidone used in Example 1 was smoothly coated on the laminate using a blade coater. When the laminate was calcined at 135°C for 2 hours, shrinkage and wrinkles occurred as in Comparative Example 4, and a smooth ferroelectric layer could not be formed, so the laminate could not proceed to the next step.
[0218] [Comparative Example 6]
[0219] Will Figure 8 The operational amplifier of the electronic circuit shown is connected to the tactile sensor made in Example 1, and the red LED is connected to a two-state touch trigger made of a delay-trigger. When the tactile sensor is touched by a finger, the voltage is turned on, and when the finger is removed, it is switched to the off state. The on state will not last ( Fig. 9 As a result, the LED does not stay lit but goes out.
[0220] [Example 8]
[0221] With a radius of curvature of 10 cm (Gaussian curvature of 0.01 cm -2 ) and on a three-dimensional support body with a convex spherical surface formed by borosilicate glass, a polyamic acid varnish liquid film of Example 4 (trade name Ecrios (registered trademark) VICT-Cz, manufactured by Mitsui Chemicals, Inc.) is coated by gravure offset printing using a soft rubber cloth, and heated at 320°C for 2 hours under an inert gas to carry out dehydration and cyclization reactions, thereby forming a polyimide film.
[0222] Next, on the polyimide film, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a first electrode of a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemical Co., Ltd.) with silver as the main component. Specifically, a brown polyimide film with a recess of 77 μm in depth is placed on a glass substrate fixed on a stainless steel table by suction using a vacuum pump, XA-9521 is filled into the recess by a scraper, and the brown polyimide film is removed, and the paste is processed by rotation and pressure on a PDMS soft rubber cloth, and the processed paste is transferred by rotation and pressure at a moving speed of 30 mm / sec to a borosilicate glass spherical surface fixed on another stainless steel table by suction and formed with the polyimide film, thereby printing an electrode. The stacked body is calcined at 150°C for 1 hour to produce a stacked body with a first electrode. The thickness of the electrode is 5.4 μm, and the volume resistivity is 4.5×10 -4 Ω·cm.
[0223] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema) as P(VDF-TrFE) with a molar ratio of 75:25 was dropwise applied to the first electrode using a syringe, and the mixture was calcined at 135°C for 2 hours under an inert gas to evaporate N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm. In addition, the Curie temperature obtained by DSC measurement of Piezotech FC25 was confirmed to be 130°C.
[0224] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemicals Co., Ltd.) with silver as the main component as the second electrode. The laminate was calcined at 120° C., which is lower than the Curie temperature, for 2 hours to produce a laminate having the second electrode formed thereon.
[0225] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 7.0 μC / cm 2 .
[0226] [Example 9]
[0227] The laminate obtained in Example 8 was used as a tactile sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The circuit diagram of the Sallen-Key low-pass filter shows that the noise is attenuated as a result. Figure 5 As shown, it was confirmed that the voltage signal was selectively extracted when the finger touched.
[0228] The tactile sensor produced in the above manner was peeled off from the spherical surface formed of borosilicate glass and attached to a spherical surface having the same Gaussian curvature of 0.01 cm as the spherical surface formed of borosilicate glass using an instant adhesive. -2 The result was a tactile sensor that conformed to the spherical surface and had no wrinkles or other appearance defects. In addition, it was confirmed that the sensor was not damaged during the peeling operation. Figure 5 Likewise, a voltage signal is generated by touching with a finger.
[0229] [Example 10]
[0230] As in Example 8, a curvature radius of 10 cm (Gaussian curvature 0.01 cm -2 ) and a polyimide film is formed on a convex spherical three-dimensional support body formed by borosilicate glass, and then, in the same manner as in Example 8, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 The first electrode was made of a stretchable paste XA-9521 (manufactured by Fujikura Chemical Co., Ltd.) with silver as the main component. The laminate was calcined at 150°C for 1 hour to produce an electrode with a thickness of 6.0 μm and a volume resistivity of 5.0×10 -5 Ω·cm first electrode.
[0231] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema), which is P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25, is dropwise applied onto the first electrode using a syringe, and the mixture is calcined at 135°C for 2 hours to evaporate the N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0232] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) was used as the second electrode. The laminate was fired at 120° C., which is lower than the Curie temperature, for 2 hours to prepare a laminate having the second electrode formed thereon.
[0233] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 7.0 μC / cm 2 .
[0234] [Example 11]
[0235] The laminate obtained in Example 10 was used as a touch sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The Sallen-Key low-pass filter shown in the circuit diagram of FIG. 1 attenuates the noise and confirms that the voltage signal is selectively extracted when a finger touches the device.
[0236] [Example 12]
[0237] With a radius of curvature of 5 cm (Gaussian curvature 0.04 cm -2 ) and on a three-dimensional support body with a convex spherical surface formed by borosilicate glass, a polyamic acid varnish liquid film of the polyimide film of Example 4 (trade name Ecrios (registered trademark), VICT-Cz, manufactured by Mitsui Chemicals, Inc.) is coated by gravure offset printing using a soft rubber cloth, and heated at 320°C for 2 hours under an inert gas to carry out dehydration and cyclization reactions, thereby forming a polyimide film.
[0238] Next, on the polyimide film, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a first electrode of a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemical Co., Ltd.) with silver as the main component. Specifically, a brown polyimide film with a recess of 77 μm in depth is placed on a glass substrate fixed on a stainless steel table by suction using a vacuum pump, the silver paste XA-9521 is filled into the recess by a scraper, and the brown polyimide film is removed, and the paste is processed by rotation and pressure on a PDMS soft rubber cloth, and the processed paste is transferred to a borosilicate glass spherical surface fixed on another stainless steel table by rotation and pressure at a moving speed of 30 mm / sec, thereby printing an electrode. The stacked body is calcined at 150°C for 1 hour to produce a stacked body with a first electrode. The thickness of the electrode is 5.4 μm, and the volume resistivity is 4.5×10 -4 Ω·cm.
[0239] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema), which is P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25, is dropwise applied onto the first electrode using a syringe, and the mixture is calcined at 135°C for 2 hours to evaporate the N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0240] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemicals Co., Ltd.) with silver as the main component as the second electrode. The laminate was calcined at 120° C., which is lower than the Curie temperature, for 2 hours to produce a laminate having the second electrode formed thereon.
[0241] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 7.0 μC / cm 2 .
[0242] [Example 13]
[0243] The laminate obtained in Example 12 was used as a touch sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The Sallen-Key low-pass filter shown in the circuit diagram of FIG. 1 attenuated the noise and confirmed that the voltage signal originating from the touch with the finger was selectively extracted.
[0244] The tactile sensor produced in the above manner was peeled off from the spherical surface formed of borosilicate glass, and attached to a spherical surface having the same Gaussian curvature of 0.04 cm as the spherical surface formed of borosilicate glass using an instant adhesive. -2 The result was a tactile sensor that had no wrinkles or other appearance defects and conformed to the spherical surface. In addition, it was confirmed that the sensor was not damaged during the peeling operation, and a voltage signal was generated by the touch of a finger.
[0245] [Example 14]
[0246] As in Example 8, a curvature radius of 10 cm (Gaussian curvature 0.01 cm -2 ) and a polyimide film is formed on a convex spherical three-dimensional support body formed of borosilicate glass, and a 0.5 cm wide and 6 cm long (area 3.0 cm) is printed on the polyimide film using an inkjet device that can be printed on a three-dimensional object. 2 The first electrode was made of silver particle ink NPS-L (manufactured by Harima Chemicals Group Co., Ltd.). The laminate was calcined at 150°C for 1 hour to produce a laminate having the first electrode. The thickness of the electrode was 0.50 μm and the volume resistivity was 1.0×10 -5 Ω·cm.
[0247] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema), which is P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25, is dropwise applied onto the first electrode using a syringe, and the mixture is calcined at 135°C for 2 hours to evaporate the N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0248] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 The laminate was calcined at 120° C., a temperature lower than the Curie temperature, for 2 hours to prepare a laminate having the second electrode formed thereon.
[0249] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 7.0 μC / cm 2 .
[0250] [Example 15]
[0251] The laminate obtained in Example 14 was used as a tactile sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The Sallen-Key low-pass filter shown in the circuit diagram of FIG. 1 attenuates the noise and confirms that the voltage signal is selectively extracted when a finger touches the device.
[0252] [Example 16]
[0253] As in Example 8, a curvature radius of 10 cm (Gaussian curvature 0.01 cm -2 ) and a polyimide film is formed on a convex spherical three-dimensional support body formed of borosilicate glass, and then a 0.5 cm wide and 6 cm long (area 3.0 cm) is printed on the polyimide film using a dispenser device that can be printed on a three-dimensional object. 2 ) was prepared by preparing a first electrode of a dispersion of PEDOT / PSS in ethanol, and the stack was calcined at 150° C. for 1 hour to produce a stack having a first electrode with an electrode thickness of 10 μm and a volume resistivity of 4.0 Ω·cm.
[0254] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema), which is P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25, is dropwise applied onto the first electrode using a syringe, and the mixture is calcined at 135°C for 2 hours to evaporate the N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0255] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 The laminate was calcined at 120° C., which is lower than the Curie temperature, for 2 hours to prepare a laminate having the second electrode formed thereon.
[0256] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 7.0 μC / cm 2 .
[0257] [Example 17]
[0258] The laminate obtained in Example 9 was used as a touch sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The Sallen-Key low-pass filter shown in the circuit diagram of FIG. 1 attenuates the noise and confirms that the voltage signal is selectively extracted when a finger touches the device.
[0259] [Example 18]
[0260] As in Example 8, a curvature radius of 10 cm (Gaussian curvature 0.01 cm -2 ) and a polyimide film is formed on a convex spherical three-dimensional support body formed by borosilicate glass, and then, in the same manner as in Example 8, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 The first electrode was made of a stretchable paste XA-9521 (manufactured by Fujikura Chemical Co., Ltd.) with silver as the main component. The laminate was calcined at 150°C for 1 hour to produce an electrode with a thickness of 5.4 μm and a volume resistivity of 4.5×10 -4 Ω·cm first electrode.
[0261] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC30 (manufactured by Arkema) as P(VDF-TrFE) with a molar ratio of 70:30 was dropwise applied to the first electrode using a syringe, and the N-methyl-2-pyrrolidone was evaporated by calcining at 135° C. for 2 hours, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm. In addition, it was confirmed that the Curie temperature obtained by DSC measurement of Piezotech FC30 was 100° C.
[0262] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemicals Co., Ltd.) with silver as the main component was used as the second electrode. The laminate was calcined at 90° C., which was lower than the Curie temperature, for 1 hour to produce a laminate having the second electrode formed thereon.
[0263] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 6.5 μC / cm 2 .
[0264] [Example 19]
[0265] The laminate obtained as above was used as a tactile sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The Sallen-Key low-pass filter shown in the circuit diagram of FIG. 1 attenuates the noise and confirms that the voltage signal is selectively extracted when a finger touches the device.
[0266] [Example 20]
[0267] As in Example 8, a curvature radius of 10 cm (Gaussian curvature 0.01 cm -2 ) and a polyimide film is formed on a convex spherical three-dimensional support body formed by borosilicate glass, and then, in the same manner as in Example 8, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 The first electrode was made of a stretchable paste XA-9521 (manufactured by Fujikura Chemical Co., Ltd.) with silver as the main component. The laminate was calcined at 150°C for 1 hour to produce an electrode with a thickness of 5.4 μm and a volume resistivity of 4.5×10 -4 Ω·cm first electrode.
[0268] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC20 (manufactured by Arkema) as P(VDF-TrFE) with a molar ratio of 80:20 was dropwise applied to the first electrode using a syringe, and the solution was calcined at 145°C for 2 hours to evaporate N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm. In addition, the Curie temperature obtained by DSC measurement of Piezotech FC20 was confirmed to be 140°C.
[0269] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemicals Co., Ltd.) with silver as the main component was used as the second electrode. The laminate was calcined at 135° C., which was lower than the Curie temperature, for 30 minutes to produce a laminate having the second electrode formed thereon.
[0270] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 8.0 μC / cm 2 .
[0271] [Example 21]
[0272] The laminate obtained in Example 13 was used as a touch sensor, the first electrode was used as a ground electrode, and then a finger was touched to the second electrode. As a result, the generation of a voltage signal was confirmed by an oscilloscope. The voltage signal was superimposed with noise from a 50 Hz commercial power supply, and the second electrode was grounded. Figure 4 The Sallen-Key low-pass filter shown in the circuit diagram of FIG. 1 attenuates the noise and confirms that the voltage signal is selectively extracted when a finger touches the device.
[0273] The tactile sensor produced in the above manner was peeled off from the spherical surface formed of borosilicate glass and attached to a spherical surface having the same Gaussian curvature of 0.01 cm as the spherical surface formed of borosilicate glass using an instant adhesive. -2 The result was a tactile sensor that had no wrinkles or other appearance defects and conformed to the spherical surface. In addition, it was confirmed that the sensor was not damaged during the peeling operation and a voltage signal was generated by contact.
[0274] [Comparative Example 6']
[0275] The radius of curvature is 10 cm (Gaussian curvature is 0.01 cm -2) and a convex spherical surface formed of borosilicate glass as a three-dimensional support, on which polyamic acid varnish, UPIA (registered trademark)-AT (trade name UPIA (registered trademark), manufactured by Ube Industries, Ltd.) is formed by soft rubber gravure offset printing, and heated at 340°C for 2 hours under inert gas to perform dehydration and cyclization reaction, thereby forming a polyimide film. Its total light transmittance is 40%. No transparency.
[0276] Next, on the polyimide film, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a first electrode of a conductive paste XA-9521 (manufactured by Fujikura Chemical Co., Ltd.) with a stretchable structure and silver as the main component. Specifically, a brown polyimide film having a concave portion with a depth of 77 μm was placed on a glass substrate fixed on a stainless steel table by suction using a vacuum pump, the silver paste XA-9521 was filled into the concave portion by a scraper, and the brown polyimide film was removed, and the paste was processed by rotation and pressure on a soft rubber cloth made of PDMS, and the processed paste was transferred by rotation and pressure at a moving speed of 30 mm / sec onto a quartz glass spherical surface fixed on another stainless steel table by suction and formed with the polyimide film, thereby printing an electrode.
[0277] The laminate was calcined at 150°C for 1 hour to prepare a laminate having a first electrode. The thickness of the electrode was 5.4 μm and the volume resistivity was 4.5×10 -4 Ω·cm.
[0278] Next, a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema), which is P(VDF-TrFE) with a molar ratio of vinylidene fluoride / trifluoroethylene of 75:25, is dropwise applied onto the first electrode using a syringe, and the mixture is calcined at 135°C for 2 hours to evaporate the N-methyl-2-pyrrolidone, thereby forming a ferroelectric layer with a thickness of 3 μm to 5 μm.
[0279] Furthermore, on the ferroelectric layer, a 0.5 cm wide and 6 cm long (area 3.0 cm 2 ) and a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemicals Co., Ltd.) with silver as the main component as the second electrode. The laminate was calcined at 120° C., which is lower than the Curie temperature, for 2 hours to produce a laminate having the second electrode formed thereon.
[0280] By applying an electric field to the ferroelectric layer via the first electrode and the second electrode, a PE curve was obtained, and the remanent polarization of the ferroelectric layer was evaluated, and the result was 7.0 μC / cm 2 .
[0281] The laminate obtained above was used as a touch sensor and was peeled off from the spherical surface formed of silica glass, and attached to a spherical surface having the same Gaussian curvature of 0.01 cm as the spherical surface formed of silica glass using an instant adhesive. -1 The brown polyimide film is hard and has low flexibility, and the wiring is damaged by repeated bending.
[0282] [Comparative Example 7]
[0283] The radius of curvature is 4.5 cm (Gaussian curvature is 0.050 cm -1 ) and a convex spherical surface formed by borosilicate glass as a three-dimensional support, a polyamic acid varnish (trade name Ecrios (registered trademark) VICT-Cz, manufactured by Mitsui Chemicals) for preparing the polyimide film of Example 4 was formed by soft rubber cloth gravure offset printing, and heated at 320°C for 2 hours to carry out dehydration and cyclization reactions, thereby forming a polyimide film, and then a first electrode was formed using a stretchable conductive paste XA-9521 (manufactured by Fujikura Chemicals Co., Ltd.) with silver as the main component in the same manner as in Example 8, and then a 12 wt% N-methyl-2-pyrrolidone solution of Piezotech FC25 (manufactured by Arkema) was dropwise applied, but a ferroelectric layer was not formed.
[0284] This application claims the priority based on Japanese application No. 2019-113906 filed on June 19, 2019, and the contents described in the claims and specification of that application are incorporated herein by reference.
[0285] Industrial Applicability
[0286] According to the tactile sensor of the present invention and the electronic circuit with a switching function using the tactile sensor, a switching device with both economy and stability and a switching function controlled by an electronic circuit can be provided with a high product yield. Since it is light, soft and strong, it can be applied to various three-dimensional shapes. The substrate is transparent so that it is inconspicuous at the location where it is configured. Thin filmization can be achieved by forming a polymer film substrate using a solution process.
Claims
1. A tactile sensor, comprising: The first electrode is printed on the surface of a polyimide film, wherein the polyimide film has a glass transition temperature of 250° C. or higher and 310° C. or lower, a tensile strength of 250 MPa or lower, an elongation of 30% or lower, a total light transmittance of 80% or higher, and a polar component of surface free energy of 1.5 mJ / m 2 ~10mJ / m 2 , and contains a structural unit represented by the following general formula (1), a ferroelectric layer printed in a manner covering the first electrode, and a second electrode which is an electrode arranged opposite to the first electrode and is printed so as to overlap with the first electrode with the ferroelectric layer interposed therebetween; X in formula (1) is selected from At least one alicyclic group in the group consisting of Y is the choice of At least one aromatic group in the group consisting of.
2. The tactile sensor according to claim 1, wherein: The polyimide film is formed at a Gaussian curvature of 0 cm -2 on the surface of the support.
3. The tactile sensor according to claim 1, wherein: The polyimide film is formed on a surface having an absolute value of 0.04 cm -2 Following the Gaussian curvature of the support surface.
4. The tactile sensor according to any one of claims 1 to 3, wherein: The product yield rate of the tactile sensor is above 99.9%.
5. The tactile sensor according to any one of claims 1 to 3, wherein: X is selected from At least one alicyclic group in the group consisting of.
6. The tactile sensor according to any one of claims 1 to 3, wherein: The main components of the first electrode and the second electrode are silver or polythiophene-based conductive polymer.
7. The tactile sensor according to any one of claims 1 to 3, wherein: The areas of the first electrode and the second electrode are 1.0×10 -2 cm 2 ~15cm 2 .
8. The tactile sensor according to any one of claims 1 to 3, wherein: The ferroelectric layer includes a vinylidene fluoride / trifluoroethylene copolymer (P(VDF-TrFE)), and the molar ratio of vinylidene fluoride (VDF) to trifluoroethylene (TrFE) in the P(VDF-TrFE) is in the range of 80 / 20 to 70 / 30.
9. The tactile sensor according to any one of claims 1 to 3, wherein: Either the first electrode or the second electrode is used as a ground electrode, and the other electrode facing the ground electrode is connected to an electronic circuit for controlling noise.
10. The tactile sensor according to claim 9, wherein: The electronic circuit for controlling noise is an active low-pass filter.
11. The tactile sensor according to claim 9, wherein: The electronic circuit for controlling noise is a comparator.
12. A switch device, which connects an electronic circuit for controlling noise to the tactile sensor according to any one of claims 1 to 11, so as to drive other devices.
13. The switching device according to claim 12, comprising: The tactile sensor according to any one of claims 1 to 11; as well as A two-state trigger connected to the electronic circuit, The on state and the off state are switched by applying deformation due to pressure to the ferroelectric layer.
14. The switching device according to claim 12 or claim 13, comprising a recognition portion that sensorily recognizes an on state and an off state of a voltage.
Citation Information
Patent Citations
JP1974065274A
Multi-controller system
JP1985008970A
Plural system type powder material preheater
JP1987059390A
Manufacture of rotor for turbine
JP1988069919A
Separation of salt in seawater
JP1989047492A